Resin particles, method for manufacturing resin particles, resin particles for toner, toner, method for manufacturing toner, developer, toner storage unit, and image forming apparatus
Patent Information
- Application Number
- JP2026043587
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2025-04-01
- Filing Date
- 2026-03-17
- Publication Date
- 2026-10-14
AI Technical Summary
【0010】 本発明によれば、環境対応性に優れ、帯電安定性、耐熱保存性、低温定着性に優れる樹脂粒子を提供することができる。
Smart Images

Figure 2026167535000012 
Figure 2026167535000013 
Figure 2026167535000001
Abstract
Description
[Technical Field]
[0001] The present invention relates to resin particles, a method for producing resin particles, resin particles for toner, toner, a method for producing toner, a developer, a toner storage unit, and an image forming apparatus. Regarding. [Background technology]
[0002] Traditionally, resin materials such as toner binders have been almost entirely dependent on petroleum resources. Petroleum-derived resins release carbon dioxide into the atmosphere when discarded, contributing to global warming. Furthermore, petroleum is a finite resource, raising concerns about its sustainable use.
[0003] Against this backdrop, there is a demand for a shift from petroleum-derived resins to environmentally friendly resins. Environmentally friendly resins include biomass resins and recycled resins. Biomass resins are made from renewable plant resources, and recycled resins are manufactured by recycling waste. By using these, the transition to sustainable materials is progressing.
[0004] As binder resins for toners, the use of environmentally friendly resins such as polyesters using plant-derived propylene glycol (a renewable resource) as a monomer, polylactic acid (PLA), rosin compounds, and recycled polyethylene terephthalate (PET) is being considered. These materials have a lower environmental impact compared to petroleum-derived resins and contribute to the manufacture of sustainable products.
[0005] On the other hand, in order to function as a toner, it needs basic properties such as low-temperature fixability, filming resistance, and heat resistance for storage. For example, a toner with excellent low-temperature fixability and filming resistance has been proposed, which contains a polyester that uses propylene glycol derived from plants, a renewable resource, as a monomer (see Patent Document 1).
[0006] Furthermore, a toner has been proposed that achieves both low-temperature fixability and heat-resistant storage by appropriately controlling the SP values of the core resin, crystalline polyester resin, and shell resin (see Patent Document 2). In addition, a toner has been proposed that allows the SP value to be controlled within an appropriate range by incorporating sulfo groups into the shell resin and adjusting the amount thereof (see Patent Document 3). [Overview of the Initiative] [Problems that the invention aims to solve]
[0007] However, the toner in Patent Document 1 uses propanediol, a short-chain hydrocarbon, as a monomer, resulting in a high SP value for the resin. Furthermore, the toners in Patent Documents 2 and 3 both have high SP values for their shell components. As a result, all of these toners have high hydrophilicity, making them prone to water absorption during high-temperature, high-humidity storage, and leading to problems with poor electrostatic properties.
[0008] The present invention aims to provide resin particles that are environmentally friendly and possess excellent electrostatic stability, heat resistance for storage, and low-temperature fixation properties. [Means for solving the problem]
[0009] The present invention relates to resin particles as described below. Resin particles containing at least a binder resin, The resin particles form a core-shell structure consisting of a core layer and a shell layer. The resin forming the core layer contains amorphous polyester resin A and crystalline polyester resin. The resin forming the shell layer contains amorphous polyester resin B. The SP values (SPa) of the amorphous polyester resin A, the SP values (SPb) of the amorphous polyester resin B, and the SP values (SPc) of the crystalline polyester resin satisfy the following relational equations (1) to (3): The resin particles contain 30% or more of environmentally friendly components. Resin particles characterized by the following features. SPa-SPc≦1.6 (1) 0.2≦SPb-SPa (2) SPb≦11.6 (3) Advantageous Effects of Invention
[0010] According to the present invention, it is possible to provide resin particles that are excellent in environmental compatibility, and excellent in charging stability, heat-resistant storage stability, and low-temperature fixability. Brief Description of Drawings
[0011] [Figure 1] Figure 1 is a schematic configuration diagram showing an example of the image forming apparatus of the present invention. [Figure 2] Figure 2 is a schematic configuration diagram showing an example of a process cartridge as the toner storage unit of the present invention. Mode for Carrying Out the Invention
[0012] (Resin Particles) The resin particles of the present invention are resin particles containing at least a binder resin, and have a core-shell structure composed of a core layer and a shell layer. The resin forming the core layer contains an amorphous polyester resin A and a crystalline polyester resin, the resin forming the shell layer contains an amorphous polyester resin B, and the content of environmentally compatible components in the resin particles is 30% or more. Further, the SP value (SPa) of the amorphous polyester resin A, the SP value (SPb) of the amorphous polyester resin B, and the SP value (SPc) of the crystalline polyester resin satisfy the following relational expressions (1) to (3). SPa-SPc≦1.6 (1) 0.2≦SPb-SPa (2) SPb≦11.6 (3)
[0013] (Amorphous Polyester Resin A) The amorphous polyester resin A in the present invention is an amorphous polyester resin obtained by polycondensation of an alcohol monomer and a carboxylic acid monomer. It is desirable that the carboxylic acid contains one or more biomass-derived dicarboxylic acids having 6 or more carbon atoms, preferably 8 or more carbon atoms.
[0014] (Amorphous polyester resin B) The amorphous polyester resin B in this invention is an amorphous polyester resin obtained by polycondensation of an alcohol component and a carboxylic acid component. It is desirable that the environmentally friendly component content be 0%.
[0015] (Method for manufacturing resin particles) The present invention provides a method for producing resin particles, comprising the following steps a, b, c, and d. Step a: A step of preparing an oil phase by dissolving or dispersing amorphous polyester resin A and crystalline polyester resin in an organic solvent. Step b: A step of adding water to the oil phase to convert the water-in-oil dispersion to an oil-in-water dispersion. Step c: A step of agglomerating the particles of the oil-in-water dispersion. Step d: After step c, an aqueous dispersion of amorphous polyester resin B is added to the aqueous dispersion to aggregate the amorphous polyester resin B and form a shell layer.
[0016] (Toner resin particles) The resin particles for toner according to the present invention contain the resin particles of the present invention.
[0017] (toner) The toner of the present invention contains the resin particles for toner of the present invention.
[0018] The aforementioned resin particles and the toner resin particles may contain other components such as mold release agents and colorants as needed.
[0019] The following describes the resin particles, the method for producing the resin particles, the resin particles for toner, the toner, the developer, the toner storage unit, and the image forming apparatus according to the present invention. It should be noted that the present invention is not limited to the embodiments shown below, and can be modified, added, altered, or deleted to the extent that a person skilled in the art can conceive of it. Any embodiment that achieves the effects and benefits of the present invention is included within the scope of the present invention.
[0020] <Environmentally friendly ingredients> In this specification, "environmentally friendly ingredients" means at least one of recycled resins and plant-derived ingredients. The resin particles have an environmentally friendly component content (A) of 30% by mass or more, and more preferably 50% by mass or more. The environmentally friendly component content (A) of 30% by mass or more is the amount required from the viewpoint of reducing environmental impact.
[0021] <<Recycled resin>> There are no particular restrictions on the recycled resin, and it can be appropriately selected depending on the purpose. Examples include recycled polyethylene terephthalate (PET) or recycled polybutylene terephthalate (PBT). The polyethylene terephthalate (PET) or polybutylene terephthalate (PBT) derived component is not particularly limited as long as it is derived from PET or PBT, and can be appropriately selected depending on the purpose. The recycled polyethylene terephthalate (PET) is generally composed of ethylene glycol and terephthalic acid. Similarly, the recycled polybutylene terephthalate (PBT) is generally composed of butylene glycol and terephthalic acid. Therefore, examples of PET or PBT-derived components include monomer units of ethylene glycol, 1,4-butanediol, or terephthalic acid.
[0022] There are no particular restrictions on the recycled PET or recycled PBT mentioned above, and they can be appropriately selected depending on the purpose. For example, recycled PET or PBT products, off-spec fiber waste, or pellets can be used. Among these, recycled products (hereinafter sometimes referred to as "recycled resin") processed into flakes are preferred.
[0023] There are no particular restrictions on the molecular weight distribution, composition, manufacturing method, and form of use of the PET or PBT used as raw materials for the aforementioned PET or PBT-derived components, and they can be appropriately selected according to the purpose.
[0024] <<Plant-derived ingredients>> The aforementioned plant-derived components are not particularly limited as long as they are plant-derived components, and can be appropriately selected according to the purpose. For example, plant-derived monomers may be used alone or in combination of two or more.
[0025] The plant-derived monomers used in this invention are not particularly limited and can be appropriately selected depending on the purpose. Examples include ethylene glycol, 1,3-propanediol, 1,3-butanediol, neopentyl glycol, adipic acid, terephthalic acid, phthalic acid, maleic acid, succinic acid, sebacic acid, dodecanedioic acid, abietic acid, and dehydroabietic acid.
[0026] <Amorphous polyester resin> As the amorphous polyester resin forming the core layer of the core-shell structure, amorphous polyester resin A described below is preferred, and as the amorphous polyester resin contained in the shell layer of the resin particles, amorphous polyester resin B described later is preferred.
[0027] <<Amorphous polyester resin A>> The amorphous polyester resin A is preferably a linear polyester resin, and more preferably an unmodified polyester resin. The amorphous polyester resin A is a polyester resin soluble in tetrahydrofuran (THF) and chloroform. The unmodified polyester resin is a polyester resin obtained using a polyhydric alcohol and a polyhydric carboxylic acid, other polyhydric carboxylic acids, or their derivatives, and is not modified by compounds or the like. The amorphous polyester resin A may be a recycled resin derived from polyethylene terephthalate or polybutylene terephthalate. By using the environmentally friendly component in at least one of the polyhydric alcohol and the polyhydric carboxylic acid or its derivative, the amorphous polyester resin A can be made the environmentally friendly component.
[0028] -Polyhydric alcohols- There are no particular restrictions on the polyhydric alcohols, and they can be appropriately selected depending on the purpose. Examples include diols. Examples of the aforementioned diols include alkylene (2-3 carbon atoms) oxide (average number of added moles 1-10) adducts of bisphenol A, ethylene glycol, 1,3-propanediol, 1,3-butanediol, 1,4-butanediol, neopentyl glycol, hydrogenated bisphenol A, or alkylene (2-3 carbon atoms) oxide (average number of added moles 1-10) adducts of hydrogenated bisphenol A. Examples of the alkylene (2-3 carbon atoms) oxide (average number of added moles 1-10) adducts of bisphenol A include polyoxypropylene (2.2)-2,2-bis(4-hydroxyphenyl)propane or polyoxyethylene (2.2)-2,2-bis(4-hydroxyphenyl)propane. These can be used individually or in combination of two or more.
[0029] The polyhydric alcohol preferably includes plant-derived ethylene glycol, plant-derived 1,3-propanediol, plant-derived 1,3-butanediol, plant-derived neopentyl glycol, recycled resin-derived ethylene glycol, and recycled resin-derived 1,4-butanediol, as this enhances environmental friendliness.
[0030] Furthermore, for the purpose of adjusting the acid value and hydroxyl value, the amorphous polyester resin A may contain trivalent or higher alcohols at the ends of its resin chains. Examples of trivalent or higher alcohols include glycerin, pentaerythritol, or trimethylolpropane. Using plant-derived glycerin is preferable because it enhances environmental friendliness.
[0031] -Components derived from polyethylene terephthalate or polybutylene terephthalate- The polyethylene terephthalate (PET) or polybutylene terephthalate (PBT) derived component is not particularly limited as long as it is derived from PET or PBT, and can be appropriately selected depending on the purpose. In the following, "polyethylene terephthalate" will be referred to as "PET," and "polybutylene terephthalate" as "PBT." The aforementioned PET is generally composed of ethylene glycol and terephthalic acid. Similarly, the aforementioned PBT is generally composed of butylene glycol and terephthalic acid. Therefore, examples of the PET or PBT-derived components include monomer units of ethylene glycol, butylene glycol, or terephthalic acid.
[0032] In terms of environmental friendliness, it is preferable to use recycled PET or recycled PBT as the aforementioned PET or PBT. There are no particular restrictions on the recycled PET or recycled PBT mentioned above, and they can be appropriately selected depending on the purpose. For example, recycled PET or PBT products, off-spec fiber waste, or pellets can be used. Among these, recycled products (hereinafter sometimes referred to as "recycled resin") processed into flakes are preferred.
[0033] There are no particular restrictions on the molecular weight distribution, composition, manufacturing method, and form of use of the PET or PBT used as raw materials for the aforementioned PET or PBT-derived components, and they can be appropriately selected according to the purpose. There are no particular restrictions on the weight-average molecular weight (Mw) of the PET or PBT mentioned above, and it can be appropriately selected depending on the purpose, but 30,000 to 100,000 is preferred.
[0034] -Polycarboxylic acids or their derivatives- The polycarboxylic acid is not particularly limited and can be appropriately selected depending on the purpose; for example, dicarboxylic acids can be used. Examples of the dicarboxylic acid include adipic acid, phthalic acid, isophthalic acid, terephthalic acid, fumaric acid, maleic acid, succinic acid, sebacic acid, dodecanedioic acid, abietic acid, dehydroabietic acid, or succinic acid substituted with an alkyl group having 1 to 20 carbon atoms or an alkenyl group having 2 to 20 carbon atoms. Examples of succinic acid substituted with the aforementioned C1-C20 alkyl group or C2-C20 alkenyl group include dodecenyl succinic acid or octyl succinic acid. There are no particular limitations on the derivative of the polycarboxylic acid, and it can be appropriately selected depending on the purpose. Examples include polycarboxylic acid anhydrides and polycarboxylic acid esters. These can be used individually or in combination of two or more.
[0035] Among these, the polycarboxylic acid preferably includes adipic acid derived from plants, terephthalic acid derived from plants, phthalic acid derived from plants, maleic acid derived from plants, succinic acid derived from plants, sebacic acid derived from plants, dodecanedioic acid derived from plants, abietic acid derived from plants, dehydroabietic acid derived from plants, and terephthalic acid derived from recycled resin. By using the polycarboxylic acid derived from plants, recycled PET, or recycled PBT, environmental compatibility can be enhanced. Furthermore, it is even more preferable to include one or more biomass-derived dicarboxylic acids with 6 or more carbon atoms as polycarboxylic acid monomers. Having 6 or more carbon atoms allows for an increase in the amount of environmentally friendly components without increasing the ester group concentration of the resin, thus enabling both electrostatic stability under high temperature and high humidity conditions and environmental compatibility.
[0036] Furthermore, for the purpose of adjusting the electrostatic properties and SP value, the amorphous polyester resin A may contain a polycarboxylic acid containing a sulfo group.
[0037] -Polyhydric carboxylic acids containing sulfogroups- Polycarboxylic acids containing sulfo groups are those that contain sulfo groups and their salt groups in the backbone of a polycarboxylic acid copolymerizable as a polyester. Examples include 5-sulfoisophthalic acid, 2-sulfoisophthalic acid, 4-sulfoisophthalic acid, 4-sulfo-2,6-naphthalenedicarboxylic acid, sulfoterephthalic acid, and their ammonium salts, lithium salts, sodium salts, potassium salts, magnesium salts, calcium salts, copper salts, and iron salts.
[0038] These polycarboxylic acids containing sulfo groups may be used individually or in combination of two or more. Among these, 5-sulfoisophthalate is preferred as the sulfonate, and sodium 5-sulfoisophthalate and potassium 5-sulfoisophthalate are particularly preferred.
[0039] There are no particular restrictions on the molar ratio of the polycarboxylic acid containing the sulfo group, and it can be appropriately selected depending on the purpose. However, it is preferably 2 mol% to 10 mol%, and more preferably 2 mol% to 5 mol%, relative to the total amount of the carboxylic acid monomer constituting the polyester resin. When the molar ratio of the dicarboxylic acid containing the sulfo group is 2 mol% or more, the electrostatic properties are excellent. When the molar ratio of monomer units having the sulfo group in the polyester resin having the sulfo group is 10 mol% or less, the cohesiveness of the polyester aqueous dispersion is increased, and the adhesion is improved when used as a shell for resin particles.
[0040] The molar ratio of the polycarboxylic acid containing the sulfo group can be measured by substituting the area of the chromatogram derived from the monomer containing the sulfonic acid base, obtained by pyrolysis gas chromatography (pyrolysis GC), into the calibration curve formula for the monomer containing the sulfonic acid base.
[0041] The fact that the resin particles contain the sulfonic acid base-containing polyester resin can be confirmed, for example, by measuring the sulfur (S) intensity by trace element analysis using X-ray fluorescence, quantifying monomers containing sulfonic acid bases by gas chromatography-mass spectrometry (GC / MS), or quantifying the sulfonic acid bases on the outermost surface of the resin particles by time-of-flight secondary ion mass spectrometry (TOF-SIMS) and qualitatively determining the resin structure on the outermost surface of the resin particles.
[0042] There are no particular restrictions on the molecular weight of the amorphous polyester resin A, and it can be appropriately selected depending on the purpose, but it is preferable that it is within the following range in GPC measurements. The weight-average molecular weight (Mw) of the amorphous polyester resin A is preferably 3,000 to 10,000, and more preferably 4,000 to 10,000. The number-average molecular weight (Mn) of the amorphous polyester resin A is preferably 1,000 to 4,000, and more preferably 1,500 to 3,000. The molecular weight ratio (Mw / Mn) of the amorphous polyester resin A is preferably 1.0 to 4.0, and more preferably 1.0 to 3.5. When the weight-average molecular weight (Mw) and number-average molecular weight (Mn) of the amorphous polyester resin A are above the lower limit of the preferred range, it is possible to suppress a decrease in the heat-resistant storage properties of the resin particles and their durability against stress such as agitation in the developing machine. Furthermore, when the weight-average molecular weight (Mw) and number-average molecular weight (Mn) of the amorphous polyester resin A are below the upper limit of the preferred range, it is possible to suppress an increase in the viscoelasticity of the resin particles when melted and suppress a decrease in low-temperature fixability.
[0043] There are no particular restrictions on the acid value of the amorphous polyester resin A, and it can be appropriately selected depending on the purpose, but 1 mg KOH / g to 50 mg KOH / g is preferred, and 5 mg KOH / g to 30 mg KOH / g is more preferred. When the acid value of the amorphous polyester resin A is 1 mg KOH / g or higher, the toner containing the resin particles tends to become negatively charged, and furthermore, when fixed to a recording medium such as paper, the affinity between the recording medium and the toner improves, and low-temperature fixing performance can be improved. In addition, when the acid value of the amorphous polyester resin A is 50 mg KOH / g or lower, it is possible to suppress a decrease in electrostatic stability, especially electrostatic stability against environmental fluctuations. The acid value of the amorphous polyester resin A can be measured in accordance with the measurement method described in JIS K0070-1992.
[0044] The hydroxyl value of the amorphous polyester resin A is not particularly limited and can be appropriately selected depending on the purpose, but it is preferably 5 mg KOH / g or higher. Furthermore, the upper limit of the hydroxyl value of the amorphous polyester resin A is not particularly limited and can be appropriately selected depending on the purpose, but it is preferably 30 mg KOH / g or lower. The lower and upper limits of the hydroxyl value of the amorphous polyester resin A can be appropriately combined, with a range of 5 mg KOH / g to 30 mg KOH / g being preferred. The hydroxyl value of the amorphous polyester resin A can be measured in accordance with the measurement method described in JIS K0070-1966.
[0045] When the amorphous polyester resin A is used as the core of the resin particles, the ratio of the hydroxyl value (OHVa) of the polyester resin A to its acid value (AVa) (OHVa / AVa) is preferably 1.1 to 1.5. If it is lower than 1.1, it is too stable and repels the shell, preventing the shell from adhering to the core. If it exceeds 1.5, the cohesiveness of the shell material is too strong, causing the cores to aggregate and become coarse.
[0046] There are no particular restrictions on the glass transition temperature (Tg) of the amorphous polyester resin A, and it can be appropriately selected depending on the purpose, but it is preferably 40°C to 80°C, and more preferably 50°C to 70°C. When the glass transition temperature (Tg) of the amorphous polyester resin A is 40°C or higher, the heat resistance and durability against stress such as agitation in the developing machine of the toner containing the resin particles are sufficient, and the filming resistance is also good. When the glass transition temperature (Tg) of the amorphous polyester resin A is 80°C or lower, the deformation due to heating and pressurization during the fixing of the toner containing the resin particles is sufficient, and the low-temperature fixing performance is good.
[0047] The molecular structure of the amorphous polyester resin A can be determined by nuclear magnetic resonance spectroscopy (NMR) in solution or solid state, as well as by X-ray diffraction, gas chromatography-mass spectrometry (GC / MS), liquid chromatography-mass spectrometry (LC / MS), or infrared absorption spectroscopy (IR). Among these, the infrared absorption spectrum obtained by IR is 965±10 cm⁻¹. -1 and 990±10cm -1 One method for detecting amorphous polyester resin A is one in which the material does not have absorption based on δCH (out-of-plane angular bending vibration) of the olefin.
[0048] The SP value (Solubility Parameter) (SPa) of the amorphous polyester resin A is not particularly limited and can be appropriately selected depending on the purpose, but it is preferably 10.8 or more and 11.4 or less, and more preferably 10.8 or more and 11.2 or less. An SP value of 10.8 or more suppresses the compatibility of the amorphous polyester resin A and the crystalline polyester resin at room temperature, resulting in good heat resistance for storage of the resin particles. An SP value of 11.4 or less results in lower hydrophilicity and improved electrostatic stability under high temperature and high humidity conditions.
[0049] The SP value (SPa) of the amorphous polyester resin A can be calculated using the following method. The SP value refers to what is called a solubility parameter (also referred to as a solubilization parameter), which is a numerical value representing how easily substances dissolve in each other. The SP value is expressed as the square root of the cohesive force between molecules, that is, the cohesive energy density CED (Cohesive Energy Density). The CED is the amount of energy required to evaporate 1 mL of a substance. The aforementioned SP value (cal / cm in the present invention 3 ) 1 / 2 can be calculated by the Fedors method using the following formula (I). SP value (solubility parameter) = (CED value) 1 / 2 = (E / V) 1 / 2 ··· Formula (I) In the aforementioned formula (I), E is the molecular cohesive energy (cal / mol), V is the molecular volume (cm 3 / mol), and when the evaporation energy of an atomic group is denoted as Δei and the molar volume as Δvi, they are respectively represented by the following formula (II) and formula (III). E=ΣΔei ··· Formula (II) V=ΣΔvi ··· Formula (III) There are various theories for the calculation method of the SP value, but in the present invention, the commonly used Fedors method is used. For this calculation method and various data of the evaporation energy Δei and molar volume Δvi of each atomic group, the data described in "Basic Theory of Adhesion" (written by Minoru Imoto, published by Kobunshi Kankokai, Chapter 5) are used.
[0050] The amount of plant-derived components in the amorphous polyester resin A can be determined by measuring the radiocarbon isotope 14 C concentration using an accelerator mass spectrometer (AMS, manufactured by Beta Analytic). By substituting the measured 14 C concentration into the following formula (4), the "plant-derived component ratio" in the resin particles can be calculated. From the viewpoint of carbon neutrality, a higher plant-derived component content is desirable. Plant-derived component ratio (%) = 14 C concentration (pMC) / 107.5×100 ··· Formula (4)
[0051] There are no particular restrictions on the content of amorphous polyester resin A in the resin particles, and it can be appropriately selected depending on the purpose, but it is preferably 50 parts by mass or more and 90 parts by mass or less, and more preferably 60 parts by mass or more and 80 parts by mass or less, per 100 parts by mass of resin particles. When the content of amorphous polyester resin A is 50 parts by mass or more per 100 parts by mass of resin particles, deterioration of the dispersibility of the pigment or release agent in the resin particles can be suppressed, and the occurrence of image fogging or distortion can be suppressed. Furthermore, when the content of amorphous polyester resin A is 90 parts by mass or less per 100 parts by mass of resin particles, the content of the crystalline resin can be prevented from decreasing, and a decrease in low-temperature fixability can be suppressed. When the content of amorphous polyester resin A is within the more preferred range described above, it is advantageous in that it is excellent in both high image quality and low-temperature fixability.
[0052] <<Amorphous polyester resin B>> The amorphous polyester resin B is preferably a linear polyester resin, and more preferably an unmodified polyester resin. The amorphous polyester resin B is a polyester resin soluble in tetrahydrofuran (THF) and chloroform. The unmodified polyester resin is a polyester resin obtained using a polyhydric alcohol and a polyhydric carboxylic acid, other polyhydric carboxylic acids, or their derivatives, and is not modified by compounds or the like. The amorphous polyester resin B may be a recycled resin derived from polyethylene terephthalate or polybutylene terephthalate. The amorphous polyester resin B can be made into the environmentally friendly component by using the environmentally friendly component in at least one of the polyhydric alcohol and the polyhydric carboxylic acid or its derivative, but it is preferable that the environmentally friendly component be 0%. Since the environmentally friendly component basically contains a lot of short-chain aliphatic hydrocarbons, not using it as a monomer lowers the ester group concentration of the resin, increases hydrophilicity, and improves the electrostatic stability under high temperature and high humidity conditions.
[0053] -Polyhydric alcohols- There are no particular restrictions on the polyhydric alcohols, and they can be appropriately selected depending on the purpose. Examples include diols. Examples of the aforementioned diols include alkylene (2-3 carbon atoms) oxide (average number of added moles 1-10) adducts of bisphenol A, ethylene glycol, 1,3-propanediol, 1,3-butanediol, 1,4-butanediol, neopentyl glycol, hydrogenated bisphenol A, or alkylene (2-3 carbon atoms) oxide (average number of added moles 1-10) adducts of hydrogenated bisphenol A. Examples of the alkylene (2-3 carbon atoms) oxide (average number of added moles 1-10) adducts of bisphenol A include polyoxypropylene (2.2)-2,2-bis(4-hydroxyphenyl)propane or polyoxyethylene (2.2)-2,2-bis(4-hydroxyphenyl)propane. These can be used individually or in combination of two or more.
[0054] Furthermore, for the purpose of adjusting the acid value and hydroxyl value, the amorphous polyester resin B may contain trivalent or higher alcohols at the ends of its resin chains. Examples of trivalent or higher alcohols include glycerin, pentaerythritol, or trimethylolpropane.
[0055] -Components derived from polyethylene terephthalate or polybutylene terephthalate- The polyethylene terephthalate (PET) or polybutylene terephthalate (PBT) derived component is not particularly limited as long as it is derived from PET or PBT, and can be appropriately selected depending on the purpose. In the following, "polyethylene terephthalate" will be referred to as "PET," and "polybutylene terephthalate" as "PBT." The aforementioned PET is generally composed of ethylene glycol and terephthalic acid. Similarly, the aforementioned PBT is generally composed of butylene glycol and terephthalic acid. Therefore, examples of the PET or PBT-derived components include monomer units of ethylene glycol, butylene glycol, or terephthalic acid.
[0056] There are no particular restrictions on the recycled PET or recycled PBT mentioned above, and they can be appropriately selected depending on the purpose. For example, recycled PET or PBT products, off-spec fiber waste, or pellets can be used. Among these, recycled products (hereinafter sometimes referred to as "recycled resin") processed into flakes are preferred.
[0057] There are no particular restrictions on the molecular weight distribution, composition, manufacturing method, and form of use of the PET or PBT used as raw materials for the aforementioned PET or PBT-derived components, and they can be appropriately selected according to the purpose. There are no particular restrictions on the weight-average molecular weight (Mw) of the PET or PBT mentioned above, and it can be appropriately selected depending on the purpose, but 30,000 to 100,000 is preferred.
[0058] -Polycarboxylic acids or their derivatives- The polycarboxylic acid is not particularly limited and can be appropriately selected depending on the purpose; for example, dicarboxylic acids can be used. Examples of the dicarboxylic acid include adipic acid, phthalic acid, isophthalic acid, terephthalic acid, fumaric acid, maleic acid, succinic acid, sebacic acid, dodecanedioic acid, abietic acid, dehydroabietic acid, or succinic acid substituted with an alkyl group having 1 to 20 carbon atoms or an alkenyl group having 2 to 20 carbon atoms. Examples of succinic acid substituted with the aforementioned C1-C20 alkyl group or C2-C20 alkenyl group include dodecenyl succinic acid or octyl succinic acid. There are no particular limitations on the derivative of the polycarboxylic acid, and it can be appropriately selected depending on the purpose. Examples include polycarboxylic acid anhydrides and polycarboxylic acid esters. These can be used individually or in combination of two or more.
[0059] As the aforementioned polycarboxylic acid, plant-derived adipic acid, plant-derived terephthalic acid, plant-derived phthalic acid, plant-derived maleic acid, plant-derived succinic acid, plant-derived sebacic acid, plant-derived dodecanedioic acid, plant-derived abietic acid, plant-derived dehydroabietic acid, or terephthalic acid derived from recycled resin may be used.
[0060] Furthermore, for the purpose of adjusting the electrostatic properties and SP value, the amorphous polyester resin B may contain a polycarboxylic acid containing a sulfo group.
[0061] -Polyhydric carboxylic acids containing sulfogroups- Polycarboxylic acids containing sulfo groups are those that contain sulfo groups and their salt groups in the backbone of a polycarboxylic acid copolymerizable as a polyester. Examples include 5-sulfoisophthalic acid, 2-sulfoisophthalic acid, 4-sulfoisophthalic acid, 4-sulfo-2,6-naphthalenedicarboxylic acid, sulfoterephthalic acid, and their ammonium salts, lithium salts, sodium salts, potassium salts, magnesium salts, calcium salts, copper salts, and iron salts.
[0062] These polycarboxylic acids containing sulfo groups may be used individually or in combination of two or more. Among these, 5-sulfoisophthalate is preferred as the sulfonate, and sodium 5-sulfoisophthalate and potassium 5-sulfoisophthalate are particularly preferred.
[0063] There are no particular restrictions on the molar ratio of the polycarboxylic acid containing the sulfo group, and it can be appropriately selected depending on the purpose. However, it is preferably 2 mol% to 10 mol%, and more preferably 2 mol% to 5 mol%, relative to the total amount of the carboxylic acid monomer constituting the polyester resin. When the molar ratio of the dicarboxylic acid containing the sulfo group is 2 mol% or more, the electrostatic properties are excellent. When the molar ratio of monomer units having the sulfo group in the polyester resin having the sulfo group is 10 mol% or less, the cohesiveness of the polyester aqueous dispersion is improved, and the adhesion is improved when used as a shell for resin particles.
[0064] The molar ratio of the polycarboxylic acid containing the sulfo group can be measured by substituting the area of the chromatogram derived from the monomer containing the sulfonic acid base, obtained by pyrolysis gas chromatography (pyrolysis GC), into the calibration curve formula for the monomer containing the sulfonic acid base.
[0065] The fact that the resin particles contain the sulfonic acid base-containing polyester resin can be confirmed, for example, by measuring the sulfur (S) intensity by trace element analysis using X-ray fluorescence, quantifying monomers containing sulfonic acid bases by gas chromatography-mass spectrometry (GC / MS), or quantifying the sulfonic acid base on the outermost surface of the resin fine particles by time-of-flight secondary ion mass spectrometry (TOF-SIMS) and qualitatively determining the resin structure on the outermost surface of the resin fine particles.
[0066] There are no particular restrictions on the molecular weight of the amorphous polyester resin B, and it can be appropriately selected depending on the purpose, but it is preferable that it is within the following range in GPC measurements. The weight-average molecular weight (Mw) of the amorphous polyester resin B is preferably 5,000 to 15,000, and more preferably 10,000 to 15,000. The number-average molecular weight (Mn) of the amorphous polyester resin B is preferably 4,500 to 14,000, and more preferably 9,000 to 14,000. The molecular weight ratio (Mw / Mn) of the amorphous polyester resin B is preferably 1.0 to 4.0, and more preferably 1.0 to 3.5. When the weight-average molecular weight (Mw) and number-average molecular weight (Mn) of the amorphous polyester resin B are above the lower limit of the preferred range, it is possible to suppress a decrease in the heat-resistant storage properties of the resin particles and their durability against stress such as agitation in the developing machine. Furthermore, when the weight-average molecular weight (Mw) and number-average molecular weight (Mn) of the amorphous polyester resin B are below the upper limit of the preferred range, it is possible to suppress an increase in the viscoelasticity of the resin particles when melted and suppress a decrease in low-temperature fixability.
[0067] There are no particular restrictions on the acid value of the amorphous polyester resin B, and it can be appropriately selected depending on the purpose, but 1 mg KOH / g to 50 mg KOH / g is preferred, and 5 mg KOH / g to 30 mg KOH / g is more preferred. When the acid value of the amorphous polyester resin B is 1 mg KOH / g or higher, the toner containing the resin particles tends to become negatively charged, and furthermore, when fixed to a recording medium such as paper, the affinity between the recording medium and the toner improves, and low-temperature fixing performance can be improved. In addition, when the acid value of the amorphous polyester resin B is 50 mg KOH / g or lower, it is possible to suppress a decrease in electrostatic stability, especially electrostatic stability against environmental fluctuations. The acid value of the amorphous polyester resin B can be measured in accordance with the measurement method described in JIS K0070-1992.
[0068] The hydroxyl value of the amorphous polyester resin B is not particularly limited and can be appropriately selected depending on the purpose, but it is preferably 5 mg KOH / g or higher. Furthermore, the upper limit of the hydroxyl value of the amorphous polyester resin B is not particularly limited and can be appropriately selected depending on the purpose, but it is preferably 30 mg KOH / g or lower. The lower and upper limits of the hydroxyl value of the amorphous polyester resin B can be appropriately combined, with a range of 5 mg KOH / g to 30 mg KOH / g being preferred. The hydroxyl value of the amorphous polyester resin B can be measured in accordance with the measurement method described in JIS K0070-1966.
[0069] When the amorphous polyester resin B is used as the core of the resin particles, the ratio of the hydroxyl value (OHVa) of the polyester resin A to its acid value (AVa) (OHVa / AVa) is preferably 1.1 to 1.5. If it is lower than 1.1, it is too stable and repels the shell, preventing the shell from adhering to the core. If it exceeds 1.5, the cohesiveness of the shell material is too strong, causing the cores to aggregate and become coarse.
[0070] There are no particular restrictions on the glass transition temperature (Tg) of the amorphous polyester resin B, and it can be appropriately selected depending on the purpose, but it is preferably 50°C to 80°C, and more preferably 50°C to 70°C. When the glass transition temperature (Tg) of the amorphous polyester resin B is 50°C or higher, the heat resistance and durability against stress such as agitation in the developing machine of the toner containing the resin particles are sufficiently improved, and the filming resistance is also good. When the glass transition temperature (Tg) of the amorphous polyester resin B is 80°C or lower, the deformation due to heating and pressurization during the fixing of the toner containing the resin particles is sufficient, resulting in good low-temperature fixing performance.
[0071] The molecular structure of the amorphous polyester resin B can be determined by nuclear magnetic resonance spectroscopy (NMR) in solution or solid state, as well as by X-ray diffraction, gas chromatography-mass spectrometry (GC / MS), liquid chromatography-mass spectrometry (LC / MS), or infrared absorption spectroscopy (IR). Among these, the infrared absorption spectrum obtained by IR is 965±10 cm⁻¹. -1 and 990±10cm -1 One method for detecting amorphous polyester resin B is one in which the material does not have absorption based on δCH (out-of-plane angular bending vibration) of the olefin.
[0072] The SP value (Solubility Parameter) (SPb) of the amorphous polyester resin B is not particularly limited and can be appropriately selected depending on the purpose, but it is preferably 11.6 or less, and more preferably 11.0 or more and 11.6 or less. An SP value of 11.0 or more suppresses the compatibility of the amorphous polyester resin B and the crystalline polyester resin at room temperature, resulting in good heat resistance for storage of the resin particles. Furthermore, an SP value of 11.6 or less results in lower hydrophilicity and improved electrostatic stability under high temperature and high humidity conditions.
[0073] The SP value (SPb) of the amorphous polyester resin B can be calculated using the following method. The SP value is a solubility parameter (also called a solubility parameter or dissolvability parameter) that quantifies how easily two substances dissolve in each other. The SP value is expressed as the square root of the cohesive energy density (CED), which is the force of attraction between molecules. The CED is the amount of energy required to evaporate 1 mL of a substance. The SP value (cal / cm²) in the present invention 3 ) 1 / 2 The calculation can be performed using the Fedors method with the following formula (I). SP value (dissolution parameter) = (CED value) 1 / 2 =(E / V) 1 / 2 Formula (I) In equation (I) above, E is the molecular cohesive energy (cal / mol) and V is the molecular volume (cm³). 3 When the vaporization energy of the atomic group is Δei and the molar volume is Δvi, the following equations (II) and (III) are used, respectively. E = ΣΔei ... Equation (II) V = ΣΔvi ... Equation (III) There are various methods for calculating SP values, but in this invention, we use Fedors' method, which is commonly used. For this calculation method, the data for the evaporation energy Δei and molar volume Δvi of each atomic group are taken from the data described in "Basic Theory of Adhesion" (by Minoru Imoto, published by Polymer Publishing Association, Chapter 5).
[0074] The amount of plant-derived components in the amorphous polyester resin B is radiocarbon isotope 14 The C concentration can be determined by measuring it using an accelerator mass spectrometer (AMS, manufactured by Beta Analytic). 14 By substituting the C concentration into the following formula (4), the "percentage of plant-derived components" in the resin particles can be calculated. From the standpoint of carbon neutrality, a higher percentage of plant-derived components is desirable. Plant-derived ingredient rate (%) = 14 C concentration (pMC) / 107.5×100...Equation (4)
[0075] There are no particular restrictions on the content of amorphous polyester resin B in the resin particles, and it can be appropriately selected depending on the purpose. However, it is preferably 5% to 40% by mass, and more preferably 10% to 40% by mass, based on the total mass of the resin particles. When the content of amorphous polyester resin B is 5% by mass or more, a sufficient effect on heat resistance and storage properties can be obtained.
[0076] <Crystalline resin> As the crystalline resin, a crystalline polyester resin is used, but other crystalline resins may be used in combination with the crystalline polyester resin. There are no particular restrictions on the other crystalline resins as long as they are crystalline, and they can be appropriately selected according to the purpose. Examples include polyurethane resin, polyurea resin, polyamide resin, polyether resin, vinyl resin, or modified crystalline resin. These may be used individually with the crystalline polyester resin, or two or more may be used together.
[0077] <<Crystalline polyester resin>> The aforementioned crystalline polyester resin (hereinafter sometimes referred to as "crystalline polyester resin C") exhibits a thermal melting characteristic in which its viscosity changes rapidly near the fixing start temperature due to its high crystallinity. The crystalline polyester resin C is insoluble in tetrahydrofuran (THF) and soluble in chloroform.
[0078] By using the crystalline polyester resin C having such properties together with the amorphous polyester resin, resin particles possessing both good heat resistance and low-temperature fixation properties can be obtained. For example, by using the crystalline polyester resin C and the amorphous polyester resin in combination, the crystalline properties of the crystalline polyester resin C provide good heat resistance until just before the melting start temperature. At the melting start temperature, the crystalline polyester resin C melts, causing a rapid decrease in viscosity (sharp melt property), which in turn causes it to become compatible with the amorphous polyester resin B. As a result, both resins rapidly decrease in viscosity, allowing for good fixation. Furthermore, good results are also shown regarding the release width (the difference between the lower limit temperature for fixation and the temperature at which high-temperature offset occurs).
[0079] The crystalline polyester resin C is obtained using a polyhydric alcohol and a polyhydric carboxylic acid or its derivative. By using the plant-derived component or the recycled PET or recycled PBT-derived component in at least one of the polyhydric alcohol and the polyhydric carboxylic acid or its derivative, the crystalline resin can be made an environmentally friendly component. These may be used individually or in combination of two or more.
[0080] There are no particular limitations on the derivative of the polycarboxylic acid, and it can be appropriately selected depending on the purpose. Examples include polycarboxylic acid anhydrides or polycarboxylic acid esters.
[0081] In this specification, the crystalline polyester resin C refers to a resin obtained using the polyhydric alcohol and the polyhydric carboxylic acid or its derivative, as described above. Modified polyester resins, such as the prepolymer, and resins obtained by subjecting the prepolymer to at least one of a crosslinking reaction and an extension reaction, do not belong to the crystalline polyester resin C.
[0082] -Polyhydric alcohols- There are no particular restrictions on the polyhydric alcohols, and they can be appropriately selected depending on the purpose. Examples include diols or alcohols with a hydride of three or more. Examples of the aforementioned diols include saturated aliphatic diols. Examples of the saturated aliphatic diol include a straight-chain saturated aliphatic diol or a branched saturated aliphatic diol.
[0083] Specific examples of the saturated aliphatic diols include ethylene glycol, 1,3-propanediol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, 1,14-tetradecanediol, 1,18-octadecanediol, or 1,14-eicosandecanediol. These may be used individually or in combination of two or more. Among these, ethylene glycol, butylene glycol, 1,4-butanediol, 1,6-hexanediol, 1,8-octanediol, 1,10-decanediol, or 1,12-dodecanediol are preferred because the crystalline polyester resin C has high crystallinity and excellent sharp-melt properties.
[0084] Among the polyhydric alcohols, those derived from plants are preferred because they can enhance environmental compatibility.
[0085] Examples of trivalent or higher alcohols include glycerin, trimethylolethane, trimethylolpropane, or pentaerythritol.
[0086] These polyhydric alcohols may be used individually or in combination of two or more.
[0087] -Polyhydric carboxylic acids- The polycarboxylic acid is not particularly limited and can be appropriately selected depending on the purpose; for example, dicarboxylic acids can be used. Examples of the dicarboxylic acid include saturated aliphatic dicarboxylic acids, unsaturated aliphatic dicarboxylic acids, or aromatic dicarboxylic acids. Examples of the saturated aliphatic dicarboxylic acid include oxalic acid, malonic acid, succinic acid, glutaric acid, sebacic acid, adipic acid, or dodecanediic acid. Examples of the aforementioned unsaturated aliphatic dicarboxylic acid include fumaric acid and maleic acid. Examples of the saturated aliphatic dicarboxylic acid include terephthalic acid. These can be used individually or in combination of two or more types.
[0088] The dicarboxylic acid is preferably a saturated aliphatic material derived from plants, having 4 to 12 carbon atoms. The plant-derived nature of the dicarboxylic acid enhances its environmental friendliness.
[0089] There are no particular restrictions on the melting point of the crystalline polyester resin C, and it can be appropriately selected depending on the purpose, but it is preferably 60°C or higher and 80°C or lower. If the melting point of the crystalline polyester resin C is 60°C or higher, it is possible to suppress the melting of the crystalline polyester resin C at low temperatures, which would reduce the heat-resistant storage properties of the resin particles. Furthermore, if the melting point of the crystalline polyester resin C is 80°C or lower, it is possible to improve the melting of the crystalline polyester resin C due to heating during fixing, and suppress the decrease in low-temperature fixing properties.
[0090] There are no particular restrictions on the molecular weight of the crystalline polyester resin C, and it can be appropriately selected depending on the purpose. However, from the viewpoint that a sharp molecular weight distribution and low molecular weight resins have excellent low-temperature fixation properties, and a high content of high molecular weight components improves heat resistance and storage properties, it is preferable that the GPC measurement of the soluble orthodichlorobenzene in the crystalline polyester resin C is within the following range. The weight-average molecular weight (Mw) of the crystalline polyester resin C is preferably 3,000 to 30,000, and more preferably 5,000 to 25,000. The number-average molecular weight (Mn) of the crystalline polyester resin C is preferably 1,000 to 10,000, and more preferably 2,000 to 10,000. The molecular weight ratio (Mw / Mn) of the crystalline polyester resin C is preferably 1.0 to 10, and more preferably 1.0 to 5.0.
[0091] There are no particular restrictions on the acid value of the crystalline polyester resin C, and it can be appropriately selected depending on the purpose. However, the lower limit of the acid value is preferably 5 mg KOH / g or higher, and more preferably 10 mg KOH / g or higher, from the viewpoint of affinity between the recording medium and the resin particles, in order to achieve the desired low-temperature fixation properties. Furthermore, the upper limit of the acid value of the crystalline polyester resin C is preferably 45 mg KOH / g or lower, from the viewpoint of improving resistance to high-temperature offset properties. The acid value of the crystalline polyester resin C can be measured in accordance with the measurement method described in JIS K0070-1992.
[0092] There are no particular restrictions on the hydroxyl value of the crystalline polyester resin C, and it can be appropriately selected depending on the purpose. However, in order to achieve the desired low-temperature fixability and good electrostatic properties, a value of 0 mg KOH / g or more and 50 mg KOH / g or less is preferred, and 0 mg KOH / g or more and 10 mg KOH / g or less is more preferred. The hydroxyl value of the crystalline polyester resin C can be measured in accordance with the measurement method described in JIS K0070-1966.
[0093] The molecular structure of the crystalline polyester resin C can be determined by nuclear magnetic resonance spectroscopy (NMR) in solution or solid state, as well as by X-ray diffraction, gas chromatography-mass spectrometry (GC / MS), liquid chromatography-mass spectrometry (LC / MS), or infrared absorption spectroscopy (IR). Among these, the infrared absorption spectrum obtained by IR is 965±10 cm⁻¹. -1 and 990±10cm -1 A simple method for detecting the crystalline polyester resin C that has absorption based on the δCH (out-of-plane bending vibration) of the olefin is to identify it as such.
[0094] The SP value (Solubility Parameter) (SPc) of the crystalline polyester resin C is not particularly limited and can be appropriately selected depending on the purpose, but a value of 9.5 or more and 10.4 or less is more preferable. An SP value of 9.5 or more suppresses the compatibility of the amorphous polyester resin B and the crystalline polyester resin at room temperature, resulting in lower hydrophilicity and improved electrostatic stability under high temperature and high humidity conditions. Furthermore, an SP value of 10.4 or less suppresses the compatibility of the crystalline polyester resin C and the amorphous polyester resin B, improving heat resistance and storage performance.
[0095] The SP value (SPc) of the aforementioned crystalline polyester resin C can be calculated by the following method. The SP value is a solubility parameter (also called a solubility parameter or dissolvability parameter) that quantifies how easily two substances dissolve in each other. The SP value is expressed as the square root of the cohesive energy density (CED), which is the force of attraction between molecules. The CED is the amount of energy required to evaporate 1 mL of a substance. The SP value (cal / cm²) in the present invention 3 ) 1 / 2 The calculation can be performed using the Fedors method with the following formula (I). SP value (dissolution parameter) = (CED value) 1 / 2 =(E / V)1 / 2 Formula (I) In equation (I) above, E is the molecular cohesive energy (cal / mol) and V is the molecular volume (cm³). 3 The values are ( / mol), and when the evaporation energy of the atomic group is Δei and the molar volume is Δvi, they are expressed by equations (II) and (III) below. E = ΣΔei ... Equation (II) V = ΣΔvi ... Equation (III) There are various methods for calculating SP values, but in this invention, we use Fedors' method, which is commonly used. For this calculation method, the data for the evaporation energy Δei and molar volume Δvi of each atomic group are taken from the data described in "Basic Theory of Adhesion" (by Minoru Imoto, published by Polymer Publishing Association, Chapter 5).
[0096] There are no particular restrictions on the content of the crystalline polyester resin C in the resin particles, and it can be appropriately selected depending on the purpose. However, it is preferably 3 parts by mass or more and 20 parts by mass or less, and more preferably 5 parts by mass or more and 15 parts by mass or less, per 100 parts by mass of the resin particles. When the content of the crystalline polyester resin C in the resin particles is 3 parts by mass or more, the sharp melting by the crystalline polyester resin C can be improved, and the low-temperature fixing properties can be improved. Furthermore, when the content of the crystalline polyester resin C in the resin particles is 20 parts by mass or less, the decrease in heat resistance and the occurrence of image fogging can be suppressed. When the content of the crystalline polyester resin C in the resin particles is within the more preferable range, it is advantageous in that it is excellent in both high image quality and low-temperature fixing properties.
[0097] <<Core-shell structure>> The resin particles preferably have a core-shell structure. The shell resin constituting the shell layer is preferably amorphous polyester resin B, and the amorphous polyester contained in the core is preferably amorphous polyester resin A. In this specification, "having a core-shell structure" means a structure having a core layer and a shell layer, "shell layer" means a layer made of resin present in the outermost layer of the resin particle, and "core layer" means the region within the resin particle excluding the shell layer. The core layer and the shell layer are formed heterogeneously, not completely incompatible with each other. In the core-shell structure described above, it is preferable that the surface of the core layer is covered by the shell layer. In the core-shell structure described above, the surface of the core layer may or may not be completely covered by the shell layer. Examples of configurations in which the surface of the core layer is not completely covered by the shell layer include a configuration in which the core layer is covered by the shell layer in a mesh-like manner, and a configuration in which the core layer is partially exposed from the shell layer. Among these, from the viewpoint of filming resistance, it is preferable that the surface of the core layer is completely covered by the shell layer.
[0098] -Shell material- The amorphous polyester resin B is used as a shell material. As mentioned above, amorphous polyester resin A is obtained by polycondensation of a polyhydric alcohol and a polyhydric carboxylic acid, and contains the environmentally friendly components. The resin for the shell is preferably a resin containing the plant-derived resin.
[0099] Methods for measuring the volume-average particle size of amorphous polyester in the aforementioned aqueous polyester dispersion include using a NanoTrac particle size distribution analyzer (UPA-EX150, Nikkiso Co., Ltd., dynamic light scattering method / laser Doppler method). First, background measurements were performed using only the dispersion solvent of each target sample dispersion. Next, the volume-average particle size could be measured by adjusting the dispersion containing each target sample to the measurement concentration range and performing the measurement.
[0100] There are no particular restrictions on the method for confirming the composition of the shell layer, and it can be appropriately selected depending on the purpose. For example, one method is to confirm it by analyzing the surface (shell layer) composition using nano-IR (also called "AMF-IR"). By using an analytical technique that combines nano-IR atomic force microscopy (AFM) with IR to achieve nanoscale resolution, the compositional structure can be determined by obtaining the IR spectrum of the surface layer (shell layer) of the resin particles.
[0101] Specifically, the resin particles are embedded in epoxy resin (S-31, manufactured by DEVCON) and cured. A cross-section is then made using a knife, and the resin particles are cut to a thickness of 60 nm using an ultrasonic ultramicrotome (Leica EM UC7, manufactured by Leica) to produce ultrathin sections of the resin particles. The prepared ultrathin sections of toner are collected on a substrate (ZnS), and the measurement area (shell layer) is measured using AFM-IR method with a nanoscale infrared spectroscopy system (e.g., nanoIR2, manufactured by Anasys Instruments). The measurement range is 1,900 cm². -1 From 910cm -1 The resolution is 2cm. -1 Therefore, the chemical structure of the measurement site (shell layer) can be analyzed from the obtained AFM-IR absorption spectrum. Thus, the composition of the surface layer (shell layer) can be confirmed by this analysis. Furthermore, by designating the measurement location as the core layer, the chemical structure of the core layer can also be analyzed.
[0102] There are no particular restrictions on the average thickness of the shell layer, and it can be appropriately selected depending on the purpose, but 50 nm to 500 nm is preferred, and 100 nm to 200 nm is more preferred. If the average thickness of the shell layer is 50 nm or more, the core layer inside the resin particles can be protected and the mechanical strength can be improved, and if it is 200 nm or less, sufficient mechanical strength can be maintained without hindering low-temperature fixation. In this specification, "average shell layer thickness" refers to the average thickness obtained by selecting 50 resin particles with a weight-average particle size within ±2.0 μm, measuring the thickness of the shell layer of each particle using the method described below, and averaging the thicknesses of the shell layers of these 50 resin particles.
[0103] There are no particular restrictions on the coverage rate of the shell layer on the surface of the core layer, and it can be appropriately selected depending on the purpose, but 50% to 100% is preferred, and 80% to 100% is more preferred. A coverage rate of 100% means that the entire surface area of the core layer in the resin particles is covered with the shell layer. The coverage rate (%) of the core layer surface by the shell layer can be calculated by the following formula (IV). Coverage rate (%) = (Area of covered region) / (Total surface area of resin particles) × 100 ... Equation (IV) In formula (IV) above, "total surface area of resin particles" means the sum of the area of the covered region and the exposed core layer area, "area of the covered region" means the area of the total surface area of resin particles in which the core layer is covered by the shell layer, and "exposed core layer area" means the area of the total surface area of resin particles in which the core layer is not covered by the shell layer.
[0104] There are no particular limitations on the method for confirming that the resin particles have a core-shell structure, and a suitable method can be selected depending on the purpose. For example, the resin particles may be embedded in epoxy resin (S-31, manufactured by DEVCON) and cured, then cross-sectioned with a knife, and excised to a thickness of 60 nm using an ultrasonic ultramicrotome (Leica EM UC7, manufactured by Leica) to prepare ultrathin sections of the resin particles. The prepared ultrathin sections of the toner are then exposed to gas with ruthenium tetroxide (RuO4) to distinguish and stain the shell and core. The gas exposure time can be adjusted as appropriate depending on the contrast during observation. Subsequently, the structure can be confirmed by observing a cross-sectional image of the resin particles using a transmission electron microscope (H-7500, manufactured by Hitachi High-Tech Corporation) at an accelerating voltage of 120 kV.
[0105] Furthermore, in the TEM images observed using the method described above, the core layer coverage area on the surface of the resin particle (the area in the resin particle where the core layer is covered by the shell layer) and the exposed core layer area (the area in the resin particle where the core layer is not covered by the shell layer) can be distinguished by the difference in brightness values. Therefore, by performing binarization processing on the TEM images observed using the method described above using image processing software, the shell layer can be identified by its contrast ratio, and the thickness of the shell layer can be measured.
[0106] Image-J can be used as the image processing software. The method for calculating the average thickness of the shell layer using Image-J is as follows. (1) Use Straight Line to draw a straight line that traces the scale. Use Analyze's Set Scale to set its actual length and units. (2) The outer circumference of a single resin particle in the cross-sectional image of the resin particle is enclosed by freehand sections to create "region 1". (3) The outer periphery of the region excluding the shell layer in the cross-sectional image of one resin particle (i.e., the boundary between the shell layer and the core layer) is enclosed with freehand sections to create "region 2". (4) Determine the center of mass of "region 1" using Analyze. (5) Using a proprietary plugin, a straight line is drawn from the outer perimeter of "region 1," that is, from the coordinates obtained by dividing the line that encloses the outer perimeter of one resin particle in (2) with Freehand-sections into 100 equally spaced sections, toward the center of gravity of the resin particle determined in (4). (6) The length obtained by subtracting the length passing through "Region 2" from the length of each of the 100 straight lines created in (5) above is calculated using the straight lines that trace the scale created in (1) above, and the average of the 100 is taken as the thickness of the shell layer of one resin particle. (7) Perform the operations described in (2) to (6) above for 50 resin particles and calculate the average thickness of the shell layer of the 50 resin particles. This average value is taken as the average thickness of the shell layer in the present invention.
[0107] Furthermore, the method for calculating the coverage rate of the shell layer using Image-J is as follows. (1) Trace the portion of the outer periphery of a single resin particle covered by the shell layer in the cross-sectional image of the resin particle using Freehand Line, and measure the length of the traced line using Analyze. This length is defined as "length 1". (2) Trace the outer circumference of one resin particle in the cross-sectional image of the resin particle using Freehand Line, and measure the length of the traced line using Analyze. This length shall be "Length 2". (3) Calculate length 1 / length 2 × 100 and use this as the coverage rate of the shell layer of one resin particle. (4) Perform the operations described in (1) to (3) above for 50 resin particles and calculate the average value of the shell layer coverage rate for the 50 resin particles. This average value is taken as the shell layer coverage rate in the present invention.
[0108] It is preferable that the SP value (SPa) of the amorphous polyester resin A and the SP value (SPc) of the crystalline polyester resin C satisfy the following relational expression (1). When (SPa-SPc) is 1.6 or less, the compatibility between the amorphous polyester resin A and the crystalline polyester resin C is increased during fixing, improving low-temperature fixing performance. SPa-SPc≦1.6 (1)
[0109] It is preferable that the SP value (SPa) of amorphous polyester resin A and the SP value (SPb) of amorphous polyester resin B satisfy the following relational expression (2). When (SPb-SPa) is 0.2 or more, amorphous polyester B can form a layered shell layer around the core, improving heat resistance and storage performance. 0.2 ≤ SPb - SPa (2)
[0110] <Other ingredients> The other components in the resin particles are not particularly limited and can be appropriately selected depending on the purpose. Examples include colorants, release agents, charge control agents, flow improvers, cleaning improvers, magnetic materials, or shape modifiers. These may be used individually or in combination of two or more.
[0111] <<Coloring agent>> There are no particular restrictions on the aforementioned colorants, and they can be appropriately selected according to the purpose. For example, carbon black, nigrosine dye, iron black, naphthol yellow S, Hansa yellow (10G, 5G, G), cadmium yellow, yellow iron oxide, yellow ochre, yellow lead, titanium yellow, polyazo yellow, oil yellow, Hansa yellow (GR, A, RN, R), pigment yellow L, benzidine yellow (G, GR), permanent yellow (NCG), Vulcan fast yellow (5G, R), tartrazine lake, quinoline yellow lake, anthrazane yellow BG L, Isoindolinone Yellow, Bengara, Red Lead, Red Lead, Cadmium Red, Cadmium Mercury Red, Antimony Red, Permanent Red 4R, Para Red, Faise Red, Parachloro-orthonitroaniline Red, Risol Fast Scarlet G, Brilliant Fast Scarlet, Brilliant Carmine BS, Permanent Red (F2R, F4R, FRL, FRLL, F4RH), Fast Scarlet VD, Belkan Fast Rubin B, Brilliant Scarlet G, Risol Rubin GX, Permanent Red F5R, Brilli Antcarmine 6B, Pigment Scarlet 3B, Bordeaux 5B, Toluidine Maroon, Permanent Bordeaux F2K, Helio Bordeaux BL, Bordeaux 10B, Bon Maroon Light, Bon Maroon Medium, Eosin Lake, Rhodamine Lake B, Rhodamine Lake Y, Alizarin Lake, Thioindigo Red B, Thioindigo Maroon, Oil Red, Quinacridone Red, Pyrazolone Red, Polyazo Red, Chrome Vermilion, Benzidine Orange, Perinon Orange, Oil Orange, Cobalt Blue, Cerulean Blue, Alkali Blue Lake, Peacock Blue Lake, Victoria Blue Lake, Metal-free Phthalocyanine Blue, Phthalocyanine Blue, Fast Sky Blue, Indanthrene Blue (RS, BC), Indigo, Ultramarine, Navy Blue, Anthraquinone Blue, Fast Violet B, Methyl Violet Lake, Cobalt Purple, Manganese Purple, Dioxane Violet, Anthraquinone Violet, Chrome Green, Zinc Green, Chromium Oxide, Pyridian, Emerald Green, Pigment Green B, Naphthol Green B, Green Gold, Acid Green Lake,Examples include malachite green lake, phthalocyanine green, anthraquinone green, titanium dioxide, zinc oxide, or lithobone. These may be used individually or in combination of two or more.
[0112] There are no particular restrictions on the content of the coloring agent in the resin particles, and it can be appropriately selected depending on the purpose, but it is preferably 1 part by mass or more and 15 parts by mass or less, and more preferably 3 parts by mass or more and 10 parts by mass or less, per 100 parts by mass of the resin particles.
[0113] The aforementioned coloring agent can also be used as a masterbatch compounded with resin. The resin used in the production of the masterbatch or kneaded together with the masterbatch is not particularly limited and can be appropriately selected depending on the purpose. For example, in addition to the amorphous polyester resin, examples include polymers of styrene or its substituted derivatives, styrene copolymers, polymethyl methacrylate, polybutyl methacrylate, polyvinyl chloride, polyvinyl acetate, polyethylene, polypropylene, polyester, epoxy resin, epoxy polyol resin, polyurethane, polyamide, polyvinyl butyral, polyacrylic acid resin, rosin, modified rosin, terpene resin, aliphatic or alicyclic hydrocarbon resin, aromatic petroleum resin, chlorinated paraffin, or paraffin wax. These may be used individually or in combination of two or more. Examples of polymers of styrene or its substituted derivatives include polystyrene, poly-p-chlorostyrene, or polyvinyltoluene. Examples of the styrene-based copolymers include styrene-p-chlorostyrene copolymer, styrene-propylene copolymer, styrene-vinyltoluene copolymer, styrene-vinylnaphthalene copolymer, styrene-methyl acrylate copolymer, styrene-ethyl acrylate copolymer, styrene-butyl acrylate copolymer, styrene-octyl acrylate copolymer, styrene-methyl methacrylate copolymer, styrene-ethyl methacrylate copolymer, styrene-butyl methacrylate copolymer, styrene-α-chloromethacrylate copolymer, styrene-acrylonitrile copolymer, styrene-vinylmethyl ketone copolymer, styrene-butadiene copolymer, styrene-isoprene copolymer, styrene-acrylonitrile-indene copolymer, styrene-maleic acid copolymer, or styrene-maleic acid ester copolymer.
[0114] There are no particular limitations on the method for producing the masterbatch, and it can be appropriately selected depending on the purpose. For example, one method involves mixing and kneading the resin for the masterbatch and the coloring agent under high shear force. In this case, an organic solvent can be used to enhance the interaction between the coloring agent and the resin. Another method, known as the flushing method, involves mixing and kneading an aqueous paste containing water from the coloring agent with the resin and an organic solvent to transfer the coloring agent to the resin side and remove the water and organic solvent components. This method is also preferably used because it allows the wet cake of the coloring agent to be used as is, eliminating the need for drying. A high-shear dispersion device such as a three-roll mill is preferably used for mixing and kneading.
[0115] <<Release agent>> The mold release agent is not particularly limited and can be appropriately selected from known ones. Examples include waxes or waxes, fatty acid amides, homopolymers or copolymers of polyacrylates, or crystalline polymers having long alkyl groups in their side chains. These may be used individually or in combination of two or more. These mold release agents are soluble in chloroform.
[0116] Examples of the aforementioned waxes include natural waxes, synthetic hydrocarbon waxes, and synthetic waxes. Examples of the aforementioned natural waxes include plant-based waxes, animal-based waxes, mineral-based waxes, and petroleum waxes. Examples of the aforementioned plant-based waxes include carnauba wax, cotton wax, or wood wax. Examples of the aforementioned animal-derived waxes include beeswax and lanolin. Examples of the aforementioned mineral waxes include ozokerite or cersine. Examples of the petroleum wax include paraffin, microcrystalline, or petrolatum. Examples of the synthetic hydrocarbon waxes include Fischer-Tropsch wax or polyethylene wax. Examples of the synthetic waxes include esters, ketones, or ethers.
[0117] Examples of the fatty acid amide include 12-hydroxystearic acid amide, stearic acid amide, phthalic anhydride, or chlorinated hydrocarbons.
[0118] Examples of the polyacrylate include poly-n-stearyl methacrylate or poly-n-lauryl methacrylate, which are low molecular weight crystalline polymer resins. Examples of the homopolymer or copolymer of the polyacrylate include a copolymer of n-stearyl acrylate and ethyl methacrylate.
[0119] Among these, plant-based waxes or ester waxes made from plant-derived materials are preferred as the mold release agent. The plant-derived nature of the mold release agent enhances environmental friendliness.
[0120] There are no particular restrictions on the melting point of the mold release agent, and it can be appropriately selected depending on the purpose, but a melting point of 60°C or higher and 80°C or lower is preferred. If the melting point of the mold release agent is 60°C or higher, it is possible to suppress the melting of the mold release agent at low temperatures, thereby suppressing a decrease in heat resistance for storage. Furthermore, if the melting point of the mold release agent is 80°C or lower, it is possible to suppress the occurrence of a fixing offset due to insufficient melting of the mold release agent when the resin has melted and is in the fixing temperature range, thereby suppressing the occurrence of image defects.
[0121] There are no particular restrictions on the content of the release agent in the resin particles, and it can be appropriately selected depending on the purpose. However, it is preferably 2 parts by mass or more and 10 parts by mass or less, and more preferably 3 parts by mass or more and 8 parts by mass or less, per 100 parts by mass of the resin particles. When the content of the release agent is 2 parts by mass or more, it is possible to suppress a decrease in high-temperature offset resistance and low-temperature fixing performance during fixing. When it is 10 parts by mass or less, it is possible to suppress a decrease in heat-resistant storage performance and suppress the occurrence of image fogging, etc. When the content of the release agent is within the more preferable range described above, it is advantageous in terms of improving image quality and fixing stability.
[0122] <<Static Control Agent>> The aforementioned charge control agent is not particularly limited and can be appropriately selected depending on the purpose. Examples include nigrosine dyes, triphenylmethane dyes, chromium-containing metal complex dyes, molybdate chelate pigments, rhodamine dyes, alkoxyamines, quaternary ammonium salts (including fluorine-modified quaternary ammonium salts), alkylamides, elemental or compound phosphorus, elemental or compound tungsten, fluorine-based surfactants, metal salicylate salts, metal salts of salicylate derivatives, metal oxynaphthoate salts, phenolic condensates, azo pigments, boron complexes, or polymer compounds having functional groups (e.g., sulfonic acid groups, carboxyl groups, or quaternary ammonium salts). These may be used individually or in combination of two or more.
[0123] The toner of the present invention may be positively charged or negatively charged, but it is preferably negatively charged.
[0124] Specific examples of the aforementioned charge control agents include Bontron 03, a nigrosine-based dye; Bontron P-51, a quaternary ammonium salt; Bontron S-34, a metal-containing azo dye; E-82, an oxynaphthoic acid-based metal complex; E-84, a salicylic acid-based metal complex; E-89, a phenolic condensate (all manufactured by Orient Chemical Industry Co., Ltd.); TP-302 and TP-415, quaternary ammonium salt molybdenum complexes (both manufactured by Hodogaya Chemical Co., Ltd.); LRA-901; LR-147, a boron complex (both manufactured by Nippon Carlit Co., Ltd.); copper phthalocyanine; perylene; quinacridone; and azo pigments.
[0125] There are no particular restrictions on the content of the charge control agent, and it can be appropriately selected according to the purpose, but it is preferably 0.1 parts by mass or more and 10 parts by mass or less, and more preferably 0.2 parts by mass to 5 parts by mass, per 100 parts by mass of the resin particles. When the content of the charge control agent is 10 parts by mass or less per 100 parts by mass of the resin particles, it is possible to prevent the toner containing the resin particles from becoming too electrostatically charged, maintain the effect of the charge control agent, prevent an increase in electrostatic attraction force with the developing roller, and suppress a decrease in the fluidity of the developer and a decrease in image density. These charge control agents can be dissolved and dispersed after melting and kneading together with the masterbatch and resin, or they can be added when directly dissolving and dispersing in an organic solvent, or they can be immobilized on the surface of the resin particles after the resin particles have been manufactured.
[0126] <<Flow improver>> The aforementioned fluidity improver is not particularly limited as long as it can be surface-treated to increase its hydrophobicity and prevent deterioration of fluidity and electrostatic properties even under high humidity conditions. It can be appropriately selected according to the purpose, and examples include silane coupling agents, silylation agents, silane coupling agents having alkyl fluoride compounds, organic titanate coupling agents, aluminum coupling agents, silicone oil, or modified silicone oil. These may be used individually or in combination of two or more.
[0127] There are no particular restrictions on the content of the fluidity improver, and it can be appropriately selected depending on the purpose, but it is preferably 0.01 parts by mass or more and 5.00 parts by mass or less, and more preferably 0.10 parts by mass or more and 2.00 parts by mass or less, per 100 parts by mass of the resin particles.
[0128] <<Cleaning performance enhancer>> The aforementioned cleaning agent is intended to remove any residual developer from the photoreceptor or primary transfer medium after transfer. The cleaning agent is not particularly limited and can be appropriately selected depending on the purpose. Examples include fatty acid metal salts or polymer fine particles. These may be used individually or in combination of two or more.
[0129] Examples of the fatty acid metal salt include zinc stearate, calcium stearate, or stearic acid.
[0130] The polymer fine particles are preferably polymer fine particles produced by soap-free emulsion polymerization, and examples include polymethyl methacrylate fine particles or polystyrene fine particles.
[0131] There are no particular restrictions on the volume-average particle size of the polymer fine particles, and they can be appropriately selected depending on the purpose. However, a relatively narrow particle size distribution is preferred, and a volume-average particle size of 0.01 μm to 1 μm is preferred.
[0132] There are no particular restrictions on the content of the cleaning performance improving agent, and it can be appropriately selected depending on the purpose, but it is preferably 0.01 parts by mass or more and 5.00 parts by mass or less, and more preferably 0.10 parts by mass or more and 2.00 parts by mass or less, per 100 parts by mass of the resin particles.
[0133] The toner of the present invention may be either magnetic toner or non-magnetic toner, but non-magnetic toner is preferred.
[0134] <<Magnetic materials>> There are no particular limitations on the magnetic material, and it can be appropriately selected depending on the purpose. Examples include iron powder, magnetite, or ferrite. These may be used individually or in combination of two or more. Among these, a white magnetic material is preferred in terms of color.
[0135] There are no particular restrictions on the content of the magnetic material, and it can be appropriately selected depending on the purpose, but it is preferably 20 parts by mass or more and 200 parts by mass or less, and more preferably 40 parts by mass or more and 150 parts by mass or less, per 100 parts by mass of the resin particles.
[0136] <<<Modifying agent>>> The aforementioned shape-modifying agent is added to modify the shape of the resin particles. There are no particular restrictions on the modifying agent, and it can be appropriately selected depending on the purpose, but it is preferable that it contains a layered inorganic mineral in which at least a portion of the interlayer ions of the layered inorganic mineral are modified with organic ions.
[0137] There are no particular limitations on the layered inorganic mineral in which at least a portion of the interlayer ions are modified with organic ions, and it can be appropriately selected according to the purpose. For example, a layered inorganic mineral having a basic smectite crystal structure modified with organic cations can be used. Smectite clay minerals have negatively charged layers, and cations exist between the layers to compensate for this. Interlayer compounds can be formed by ion exchange of these cations or adsorption of polar molecules. In addition, metal ions can be introduced by substituting some of the divalent metals in the layered inorganic mineral with trivalent metals. However, since introducing metal anions increases hydrophilicity, layered inorganic compounds in which at least a portion of the metal anions are modified with organic anions are preferred.
[0138] The layered inorganic mineral, in which at least a portion of the interlayer ions of the aforementioned layered inorganic mineral are modified with organic ions, can be obtained by using an organic cation modifier or an organic anion modifier.
[0139] The organic cation modifier is not particularly limited as long as it can be modified by organic ions as described above, and examples include quaternary alkylammonium salts, phosphonium salts, or imidazolium salts. These may be used individually or in combination of two or more. Among these, quaternary alkylammonium salts are preferred as the organic cation modifier.
[0140] The quaternary alkylammonium is not particularly limited, and examples include trimethylstearylammonium, dimethylstearylbenzylammonium, or oleylbis(2-hydroxyethyl)methylammonium.
[0141] The organic anion modifier is not particularly limited as long as it can be modified by organic ions as described above. Examples include sulfates, sulfonates, carboxylates, or phosphates having branched, unbranched, or cyclic alkyl (C1-C44) groups, branched, unbranched, or cyclic alkenyl (C1-C22) groups, branched, unbranched, or cyclic alkoxy (C8-C32) groups, branched, unbranched, or cyclic hydroxyalkyl (C2-C22) groups, an ethylene oxide skeleton, or a propylene oxide skeleton. These may be used individually or in combination of two or more. Among these, the organic anion modifier is preferably a carboxylic acid having an ethylene oxide skeleton.
[0142] When the resin particles are manufactured by the method described later (method for manufacturing resin particles), the aforementioned shape-reforming agent is preferably added in the "oil phase preparation step" described later. By modifying at least a portion of the interlayer ions of the layered inorganic mineral with organic ions, the material has appropriate hydrophobicity, so that the oil phase containing the resin particle material has non-Newtonian viscosity, and the resin particles can be deformed. In this case, the content of the deforming agent in the resin particle material is preferably 0.05% to 10% by mass, and more preferably 0.05% to 5% by mass, based on the total amount of the resin particle material.
[0143] Furthermore, there are no particular limitations on the layered inorganic mineral, and it can be appropriately selected depending on the purpose. Examples include montmorillonite, bentonite, hectorite, attapulgite, sepiolite, or mixtures thereof. Among these, layered inorganic minerals in which at least a portion of the interlayer ions are modified with organic ions are preferred because, when the resin particles are used in toner, they do not affect the toner characteristics, the viscosity can be easily adjusted, and the amount added can be small. Therefore, organically modified montmorillonite or organically modified bentonite is preferred.
[0144] Commercially available layered inorganic minerals in which at least a portion of the interlayer ions of the aforementioned layered inorganic mineral are modified with organic ions include, for example, quaternium-18 bentonite such as Bentone 3, Bentone 38, Bentone 38V (all manufactured by Rheox), Thixogel VP (manufactured by United Catalyst), Kraton 34, Kraton 40, Kraton XL (all manufactured by Southern Clay); stearalkonium bentonite such as Bentone 27 (manufactured by Rheox), Thixogel LG (manufactured by United Catalyst), Kraton AF, Kraton APA (all manufactured by Southern Clay); and quaternium-18 / benzalkonium bentonite such as Kraton HT, Kraton PS (both manufactured by Southern Clay). Among these, Kraton AF and Kraton APA are preferred.
[0145] Furthermore, as a layered inorganic mineral in which at least a portion of the interlayer ions of the aforementioned layered inorganic mineral are modified with organic ions, a more preferable option is DHT-4A(registered trademark) (manufactured by Kyowa Chemical Industry Co., Ltd.) modified with an organic anion modifier represented by the following general formula (V). An example of an organic anion modifier represented by the following general formula (V) is Hythenol(registered trademark) 330T (manufactured by Daiichi Kogyo Seiyaku Co., Ltd.).
[0146] R1(OR2) n OSO3M...General formula (V) (In the above general formula (V), R1 represents an alkyl group having 13 carbon atoms, R2 represents an alkylene group having 2 to 6 carbon atoms, n represents an integer from 2 to 10, and M represents a monovalent metallic element.)
[0147] -Volume-average particle size of resin particles- There are no particular restrictions on the volume-average particle size (D4) of the resin particles, and it can be appropriately selected depending on the purpose, but it is preferably 3 μm or more and 7 μm or less. Furthermore, there are no particular restrictions on the ratio (D4 / Dn) of the volume-average particle size (D4) of the resin particles to the number-average particle size (Dn) of the resin particles, and it can be appropriately selected depending on the purpose, but it is preferably 1.2 or less. Furthermore, it is preferable that the resin particles contain at least 1% to 10% of a component having a volume-average particle size of 2 μm or less.
[0148] The volume-average particle size (D4), number-average particle size (Dn), and their ratio (D4 / Dn) of the aforementioned resin particles can be measured using, for example, a Coulter Multisizer 3 (manufactured by Beckman Coulter). In this specification, the values obtained using the Coulter Multisizer 3 will be used. The measurement method is described below.
[0149] First, a mixture is obtained by adding 0.1 mL to 5 mL of a surfactant (preferably polyoxyethylene alkyl ether (a nonionic surfactant)) as a dispersant to 100 mL to 150 mL of an electrolytic aqueous solution. To this mixture, 2 mg to 20 mg of the sample to be measured is added. The electrolytic aqueous solution in which the sample to be measured is suspended is dispersed in an ultrasonic disperser for about 1 to 3 minutes. The volume and number of the resin particles are measured using the measuring device (Coulter Multisizer 3) with a 100 μm aperture, and the volume distribution and number distribution are calculated. From the obtained distribution, the volume-average particle size (D4) and number-average particle size (Dn) of the resin particles can be determined. The electrolytic aqueous solution mentioned above is a 1% by mass sodium hydrochloride aqueous solution prepared using primary sodium chloride. For example, ISOTON-3 (manufactured by Beckman Coulter) can be used.
[0150] The 13 channels used are: 2.00 μm to less than 2.52 μm, 2.52 μm to less than 3.17 μm; 3.17 μm to less than 4.00 μm, 4.00 μm to less than 5.04 μm, 5.04 μm to less than 6.35 μm, 6.35 μm to less than 8.00 μm, 8.00 μm to less than 10.08 μm, 10.08 μm to less than 12.70 μm, 12.70 μm to less than 16.00 μm, 16.00 μm to less than 20.20 μm, 20.20 μm to less than 25.40 μm, 25.40 μm to less than 32.00 μm, and 32.00 μm to less than 40.30 μm.
[0151] -Glass transition temperature (Tg) and melting point (Tm)- --Method for measuring glass transition temperature (Tg) and melting point (Tm)-- The glass transition temperature (Tg) and melting point (Tm) as used herein can be measured, for example, using a DSC system (differential scanning calorimeter) ("Q-200", manufactured by TA Instruments). Specifically, the glass transition temperature (Tg) and melting point (Tm) of the target sample can be measured by the following procedure. First, approximately 5.0 mg of the target sample is placed in an aluminum sample container, which is then placed on a holder unit and set in an electric furnace. Next, under a nitrogen atmosphere, the sample is heated from -80°C to 150°C at a heating rate of 10°C / min (first heating pass). After that, it is cooled from 150°C to -80°C at a cooling rate of 10°C / min, and then heated again to 150°C at a heating rate of 10°C / min (second heating pass). During both the first and second heating passes, a differential scanning calorimeter ("Q-200", manufactured by TA Instruments Inc.) is used to measure the DSC curve.
[0152] From the obtained DSC curves, the analysis program in the Q-200 system can be used to select the DSC curve for the first heating cycle and determine the glass transition temperature of the target sample during the first heating cycle. Similarly, the DSC curve for the second heating cycle can be selected to determine the glass transition temperature of the target sample during the second heating cycle.
[0153] Furthermore, using the analysis program in the Q-200 system, the DSC curve obtained can be selected for the first heating cycle, and the endothermic peak top temperature of the target sample during the first heating cycle can be determined as the melting point. Similarly, the DSC curve obtained for the second heating cycle can be selected, and the endothermic peak top temperature of the target sample during the second heating cycle can be determined as the melting point.
[0154] In this specification, when the resin particles are used as the target sample, the glass transition temperature during the first heating is defined as [Tg1st], and the glass transition temperature during the second heating is defined as [Tg2nd]. Furthermore, in this specification, unless otherwise specified, the glass transition temperature and melting point of the amorphous polyester resin A, amorphous polyester resin B, crystalline polyester resin C, and other components such as the mold release agent are defined as follows: the endothermic peak top temperature during the second heating is defined as the melting point of each sample, and the Tg during the second heating is defined as the Tg of each sample.
[0155] --Tg1st (resin particles)-- There are no particular restrictions on the glass transition temperature [Tg1st(resin particles)] during the first heating step of differential scanning calorimetry (DSC) of the resin particles, and it can be appropriately selected according to the purpose. However, from the viewpoint of low-temperature fixability, it is preferably 20°C to 50°C, and more preferably 35°C to 45°C. If the [Tg1st(resin particles)] is 20°C or higher, a decrease in heat resistance for storage, blocking in the developing machine, and filming on the photoreceptor can be suppressed. If the [Tg1st(resin particles)] is 50°C or lower, a decrease in the low-temperature fixability of the resin particles can be suppressed.
[0156] Conventionally, when the glass transition temperature (Tg) of toner is around 50°C or below, toner aggregation is more likely to occur due to temperature changes during transportation and storage, especially in summer or tropical regions. As a result, solidification occurs in the toner bottle and toner adheres to the developing machine. Furthermore, toner clogging in the toner bottle can lead to poor replenishment, and toner adherence to the developing machine can easily cause image abnormalities.
[0157] Even if the toner containing the aforementioned resin particles has a lower glass transition temperature (Tg) than conventional toners, if the amorphous polyester resin A, which is the low Tg component in the toner, is nonlinear, the toner can maintain its heat resistance for storage. In particular, if the amorphous polyester resin A has urethane bonds or urea bonds with high cohesive force, the effect of maintaining heat resistance for storage becomes even more pronounced.
[0158] --[Tg2nd (resin particles)]-- There are no particular restrictions on the glass transition temperature [Tg2nd(resin particles)] during the second heating step of differential scanning calorimetry (DSC) of the resin particles, and it can be appropriately selected according to the purpose, but it is preferably 0°C to 30°C, and more preferably 0°C to 15°C. If the [Tg2nd(resin particles)] is 0°C or higher, it is possible to suppress a decrease in the blocking resistance of the fixed image (printed material), and if it is 30°C or lower, it is possible to suppress a decrease in low-temperature fixability and glossiness. The value of [Tg2nd (resin particles)] can be adjusted, for example, by the Tg of the crystalline resin and the amount added.
[0159] --Difference [[Tg1st (resin particles)]-[Tg2nd (resin particles)]]-- The difference between the glass transition temperature [Tg1st(resin particle)] during the first heating step and the glass transition temperature [Tg2nd(resin particle)] during the second heating step of differential scanning calorimetry (DSC) of the resin particles [Tg1st(resin particle)] is not particularly limited and can be appropriately selected depending on the purpose, but it is preferably 10°C or higher. The upper limit of the difference [Tg1st(resin particle)] - [Tg2nd(resin particle)] is not particularly limited and can be appropriately selected depending on the purpose, but it is preferably 50°C or lower.
[0160] A difference of 10°C or more between Tg1st (resin particles) and Tg2nd (resin particles) is advantageous in that it provides superior low-temperature fixation. Furthermore, a difference of 10°C or more between Tg1st (resin particles) and Tg2nd (resin particles) means that the crystalline polyester resin C, amorphous polyester resin A, and amorphous polyester resin B, which were in an immiscible state before heating (before the first heating), become miscible after heating (after the first heating). Note that the miscible state after heating does not need to be a perfectly miscible state.
[0161] --Tg2nd (THF-insoluble components)-- The glass transition temperature [Tg2nd(THF-insoluble portion)] in the second heating step of differential scanning calorimetry (DSC) of the tetrahydrofuran (THF)-insoluble portion of the resin particles is not particularly limited and can be appropriately selected according to the purpose, but it is preferably -40°C to 30°C and more preferably 0°C to 20°C. If the [Tg2nd(THF-insoluble portion)] is -40°C or higher, the advantage is that a decrease in the blocking resistance of the fixed image (printed material) can be suppressed, and if it is 30°C or lower, the advantage is that a decrease in low-temperature fixability and glossiness can be suppressed.
[0162] The value of [Tg2nd (THF-insoluble)] can be adjusted, for example, by changing the number of carbon atoms in the polyhydric alcohol and polyhydric carboxylic acid of amorphous polyester resin A.
[0163] --Melting point (Tm)-- There are no particular restrictions on the melting point (Tm) of the resin particles, and it can be appropriately selected depending on the purpose, but it is preferably 60°C or higher and 80°C or lower.
[0164] -Storage modulus- --Method for measuring the storage modulus G'-- The storage modulus (G') under various conditions can be measured, for example, using a dynamic viscoelasticity measuring device (ARES, manufactured by TA Instruments). The measurement frequency is 1 Hz. Specifically, the sample to be measured is molded into a pellet with a diameter of 8 mm and a thickness of 1 mm to 2 mm, fixed to an 8 mm diameter parallel plate, stabilized at 40°C, and then heated to 200°C at a heating rate of 2.0°C / min with a frequency of 1 Hz (6.28 rad / s) and a strain of 0.1% (strain control mode), and the storage modulus is measured. In this specification, the storage modulus at 40°C is sometimes represented as [G'(40)], and the storage modulus at 100°C is sometimes represented as [G'(100)].
[0165] --[G'(100)(THF-insoluble)], and [[G'(40)(THF-insoluble)] / [G'(100)(THF-insoluble)]]-- There are no particular restrictions on the storage modulus at 100°C of the tetrahydrofuran (THF)-insoluble portion of the resin particles [G'(100)(THF-insoluble portion)], and it can be appropriately selected depending on the purpose, but 1.0 × 10 5 Pa~1.0×10 7 Pa is preferred, 5.0 × 10 5 Pa~5.0×10 6 Pa is more preferable. When the storage modulus [G'(100)(THF-insoluble)] is within the more preferable range, it is advantageous in that it provides better low-temperature fixation.
[0166] There are no particular restrictions on the ratio of the storage modulus of the THF-insoluble portion of the resin particles between the storage modulus at 40°C [G'(40)(THF-insoluble portion)] and the storage modulus at 100°C [G'(100)(THF-insoluble portion)] [G'(40)(THF-insoluble portion)] / [G'(100)(THF-insoluble portion)], and it can be appropriately selected depending on the purpose, but it is preferably 3.5 × 10 or less. When the ratio [G'(40)(THF-insoluble portion)] / [G'(100)(THF-insoluble portion)] is 3.5 × 10 or less, the decrease in low-temperature fixability can be suppressed.
[0167] Furthermore, the resin particles have a [G'(100)(THF insoluble content)] of 1.0 × 10 5 Pa~1.0×10 7 When the value is Pa and the ratio [[G'(40)(THF insoluble)] / [G'(100)(THF insoluble)]] is 3.5 × 10 or less, it is advantageous in that it promotes compatibility between the crystalline resin and the amorphous polyester resin which has a high Tg component, lowers the 1 / 2 outflow temperature measured by a thermal fluid evaluation device (flow tester), and improves image gloss.
[0168] The values of [G'(100)(THF-insoluble)] and [G'(40)(THF-insoluble)] can be adjusted, for example, by the resin composition (bifunctional or higher polyhydric alcohol and bifunctional or higher acidic component). Specifically, adjustments can be made, for example, as follows: To increase the storage modulus (G'), adjustments can be made by shortening the distance of ester bonds in the resin or by using a resin composition that includes aromatic rings. To decrease the storage modulus (G'), adjustments can be made by using a linear polyester resin or by using a polyhydric alcohol with alkyl groups in its side chains as a component of the polyester resin.
[0169] --THF insoluble matter-- The THF-insoluble portion of the aforementioned resin particles can be obtained as follows. It is obtained by adding 1 part resin particles to 100 parts tetrahydrofuran (THF), refluxing for 6 hours, and then separating the insoluble components from the supernatant liquid by centrifugation.
[0170] - Measuring molecular weight - The molecular weight of each component of the aforementioned resin particles can be measured, for example, under the following analytical conditions. [Analysis conditions] • Gel permeation chromatography (GPC) measuring device: GPC-8220GPC (manufactured by Tosoh Corporation) Column: TSKgel® SuperHZM-H 15cm 3-row (manufactured by Tosoh Corporation) ·Temperature: 40℃ • Detector: RI (refractive index) detector • Solvent: Chloroform Flow rate: 0.35 mL / min • Sample: Inject 100 μL of 0.1% by mass of the sample. • Sample pretreatment: The resin particles are dissolved in chloroform at a concentration of 0.1% by mass. The solution is then stirred at 25°C for 30 minutes to obtain a solution in which the soluble components have dissolved. This solution is filtered through a membrane filter with a mesh size of 0.2 μm, and the filtrate is used as the chloroform sample solution. 100 μL of the chloroform sample solution is injected and measured.
[0171] For molecular weight measurement of a sample, the molecular weight distribution of the sample is calculated from the relationship between the logarithm of a calibration curve prepared using several monodisperse polystyrene standard samples and the count. Examples of standard polystyrene samples used for preparing the calibration curve include Showdex® STANDARD (manufactured by Showa Denko K.K.) Std. Nos S-6550, S-1700, S-740, S-321, S-129, S-10, S-2.9, and S-0.6.
[0172] There are no particular restrictions on the method for producing the polyester aqueous dispersion, but it is preferable to produce it by the method for producing the polyester aqueous dispersion of the present invention, which will be described later.
[0173] (Method for producing a polyester aqueous dispersion) A method for producing a polyester aqueous dispersion includes a) a step of preparing an oil phase by dissolving or dispersing an amorphous polyester resin in an organic solvent (hereinafter sometimes referred to as the "oil phase preparation step"), and b) a step of adding an aqueous medium to the oil phase to invert the water-in-oil dispersion into an oil-in-water dispersion (hereinafter sometimes referred to as the "phase inversion emulsification step"), and further, if necessary, other steps such as an aqueous phase preparation step and a solvent removal step.
[0174] <Oil phase preparation process> The aforementioned oil phase preparation step is a step of preparing an oil phase by dissolving or dispersing an amorphous polyester resin in an organic solvent.
[0175] There are no particular restrictions on the organic solvent, and it can be appropriately selected depending on the purpose, but an organic solvent with a boiling point of less than 150°C is preferred because it is easy to remove. The organic solvent with a boiling point of less than 150°C is not particularly limited and can be appropriately selected depending on the purpose. Examples include toluene, xylene, benzene, carbon tetrachloride, methylene chloride, 1,2-dichloroethane, 1,1,2-trichloroethane, trichloroethylene, chloroform, monochlorobenzene, dichloroethylidene, methyl acetate, ethyl acetate, methyl ethyl ketone, or methyl isobutyl ketone. These may be used individually or in combination of two or more. Among these, ethyl acetate, toluene, xylene, benzene, methylene chloride, 1,2-dichloroethane, chloroform, or carbon tetrachloride are preferred as the organic solvent, with ethyl acetate being more preferred.
[0176] There are no particular restrictions on the amount of the organic solvent used, and it can be appropriately selected depending on the purpose, but it is preferably 40 parts by mass or more and 300 parts by mass or less, more preferably 60 parts by mass or more and 140 parts by mass or less, and even more preferably 80 parts by mass or more and 120 parts by mass or less, per 100 parts by mass of the raw material for the resin particles.
[0177] There are no particular restrictions on the method for preparing the oil phase, and it can be appropriately selected depending on the purpose. For example, one method is to gradually add the materials for the oil phase to the organic solvent while stirring, and dissolve or disperse them. For the aforementioned dispersion, known methods can be used, such as dispersers like bead mills or disc mills.
[0178] <Aqueous phase (aqueous medium) production process> The aforementioned aqueous phase preparation step is a step of preparing an aqueous phase (aqueous medium). The aqueous medium is not particularly limited and can be appropriately selected depending on the purpose. Examples include water, a solvent miscible with water, or a mixture thereof. These may be used individually or in combination of two or more. Among these, water is preferred.
[0179] The solvent that can be miscible with water is not particularly limited and can be appropriately selected depending on the purpose. Examples include alcohols, dimethylformamide, tetrahydrofuran, ethyl acetate, cellosolves, or lower ketones. The aforementioned alcohol is not particularly limited and can be appropriately selected depending on the purpose. Examples include methanol, isopropanol, or ethylene glycol. The aforementioned lower ketones are not particularly limited and can be appropriately selected depending on the purpose. Examples include acetone or methyl ethyl ketone.
[0180] <Phase inversion emulsification process> The phase inversion emulsification step involves adding an aqueous medium to the oil phase to invert the water-in-oil dispersion into an oil-in-water dispersion. This yields a polyester aqueous dispersion (oil droplets).
[0181] There are no particular limitations on the method for phase-inversion emulsification of the amorphous polyester resin A in the aqueous medium, and a suitable method can be selected depending on the purpose. For example, one method involves neutralizing the oil phase with a base, adding the aqueous phase thereto, and obtaining a polyester aqueous dispersion by phase-inversion emulsification, which converts the water-in-oil dispersion to an oil-in-water dispersion.
[0182] Either a basic inorganic compound or a basic organic compound may be used as the base for neutralizing the oil phase. Examples of basic inorganic compounds include sodium hydroxide, potassium hydroxide, lithium hydroxide, ammonia, sodium carbonate, sodium bicarbonate, potassium carbonate, potassium bicarbonate, and ammonia. Examples of basic organic compounds include N,N-dimethylethanolamine, N,N-diethylethanolamine, triethanolamine, trippropanolamine, tributanolamine, triethylamine, n-propylamine, n-butylamine, isopropylamine, monomethanolamine, morpholine, methoxypropylamine, pyridine, vinylpyridine, and isophoronediamine.
[0183] Neutralization is carried out using a conventional stirrer or dispersion device to ensure uniform mixing and dispersion. There are no particular limitations on the dispersion device, but examples include ultrasonic dispersers, bead mills, ball mills, roll mills, homomixers, ultramixers, disper mixers, through-type high-pressure dispersion devices, impact-type high-pressure dispersion devices, porous high-pressure dispersion devices, ultra-high-pressure homogenizers, and ultrasonic homogenizers. A conventional stirrer and dispersion device may be used in combination.
[0184] There are no particular restrictions on the amount of the aqueous medium used when emulsifying the oil phase containing the amorphous polyester resin A, and it can be appropriately selected according to the purpose. Preferably, the amount is 50 parts by mass or more and 2,000 parts by mass or less, and more preferably 100 parts by mass or more and 1,000 parts by mass or less, per 100 parts by mass of the amorphous polyester resin A. If the amount of the aqueous medium used is 50 parts by mass or more per 100 parts by mass of the amorphous polyester resin A, it is possible to prevent the dispersion state of the resin particle material from deteriorating and to suppress the inability to obtain a polyester aqueous dispersion with a predetermined particle size. Furthermore, if the amount of the aqueous medium used is 2,000 parts by mass or less per 100 parts by mass of the amorphous polyester resin A, it is possible to suppress the increase in production costs.
[0185] When inverting the oil phase containing the amorphous polyester resin A, a dispersant may be used to stabilize the dispersion, such as oil droplets, to achieve the desired shape and sharpen the particle size distribution. There are no particular restrictions on the dispersant, and it can be appropriately selected depending on the purpose. Examples include surfactants, poorly water-soluble inorganic compound dispersants, or polymer-based protective colloids. These may be used individually or in combination of two or more. Among these, surfactants are preferred as the dispersant.
[0186] The surfactant is not particularly limited and can be appropriately selected depending on the purpose. Examples include anionic surfactants, cationic surfactants, nonionic surfactants, or amphoteric surfactants.
[0187] The anionic surfactant is not particularly limited and can be appropriately selected depending on the purpose. Examples include alkyl sulfates, alkylbenzene sulfonates, α-olefin sulfonates, or phosphate esters. Among these, alkyl sulfates are preferred because they do not easily form agglomerates during the resin particle production process, thus broadening the selectivity of agglomerates.
[0188] The amount of surfactant is preferably 0% by mass or more and 3.0% by mass or less based on 100% by mass of resin particles. If it exceeds 3.0% by mass, the shell material becomes too stable and does not adhere well to the core, and the electrostatic charge of the resin particles becomes uneven.
[0189] The aforementioned phase inversion emulsification can be carried out using a stirring blade. The aforementioned stirring blades are not particularly limited and can be appropriately selected according to the viscosity of the solution. Examples include anchor blades, turbine blades, Faudler blades, full-zone blades, Maxblend blades, or crescent blades.
[0190] When using the aforementioned stirring blade, there are no particular restrictions on the peripheral speed, and it can be appropriately selected according to the purpose, but 0.4 m / sec to 2.0 m / sec is preferred, and 0.7 m / sec to 1.5 m / sec is more preferred.
[0191] There are no particular restrictions on the volume-average particle size of the polyester aqueous dispersion (oil droplets) and it can be appropriately selected depending on the purpose, but 20 nm to 200 nm is preferred, and 20 nm to 100 nm is more preferred.
[0192] <Solvent removal process> The solvent removal step is a step of removing the organic solvent from the polyester aqueous dispersion obtained in the phase inversion emulsification step.
[0193] There are no particular limitations on the method for removing the organic solvent from the polyester aqueous dispersion, and a suitable method can be selected depending on the purpose. Examples include gradually raising the temperature of the entire reaction system to evaporate the organic solvent in the fine particle dispersion (oil droplets); spraying the fine particle dispersion into a dry atmosphere to remove the organic solvent in the fine particle dispersion (oil droplets); or reducing the pressure of the fine particle dispersion to evaporate and remove the organic solvent. These methods may be used individually or in combination of two or more.
[0194] There are no particular restrictions on the drying atmosphere in which the fine particle dispersion is sprayed, and it can be appropriately selected depending on the purpose. Examples include heated air, nitrogen, carbon dioxide, combustion gas, etc. In general, various gas streams heated to a temperature above the boiling point of the highest boiling point solvent used are used.
[0195] The solvent removal process can be carried out using equipment, such as a spray dryer, belt dryer, or rotary kiln, and the desired quality can be obtained in a short processing time.
[0196] (Method for manufacturing resin particles) The present invention provides a method for producing resin particles, which includes a) a step of preparing an oil phase by dissolving or dispersing at least an amorphous polyester resin in an organic solvent (hereinafter sometimes referred to as the "oil phase preparation step"), b) a step of adding an aqueous medium to the oil phase to invert the water-in-oil dispersion into an oil-in-water dispersion (hereinafter sometimes referred to as the "phase inversion emulsification step"), c) a step of agglomerating the particles of the oil-in-water dispersion to obtain resin particles (hereinafter sometimes referred to as the "aggregation step"), and a step of forming a shell layer, and further, if necessary, other steps such as an aqueous phase preparation step, a solvent removal step, a fusion step, a washing step, a drying step, a classification step, and an annealing step.
[0197] <Oil phase preparation process> The oil phase preparation step is a step of preparing an oil phase in which at least an amorphous polyester resin is dissolved or dispersed in an organic solvent. The amorphous polyester resin is as described in the section <Amorphous Polyester Resin B> of (Polyester Aqueous Dispersion, Resin Particles, Toner Resin, and Paint Resin Particles), and the oil phase preferably contains the amorphous polyester resin B. The oil phase may further contain, if necessary, the crystalline resin, the coloring agent, the mold release agent, and the like.
[0198] There are no particular restrictions on the organic solvent, and it can be appropriately selected depending on the purpose, but an organic solvent with a boiling point of less than 150°C is preferred because it is easy to remove. The organic solvent with a boiling point of less than 150°C is not particularly limited and can be appropriately selected depending on the purpose. Examples include toluene, xylene, benzene, carbon tetrachloride, methylene chloride, 1,2-dichloroethane, 1,1,2-trichloroethane, trichloroethylene, chloroform, monochlorobenzene, dichloroethylidene, methyl acetate, ethyl acetate, methyl ethyl ketone, or methyl isobutyl ketone. These may be used individually or in combination of two or more. Among these, ethyl acetate, toluene, xylene, benzene, methylene chloride, 1,2-dichloroethane, chloroform, or carbon tetrachloride are preferred as the organic solvent, with ethyl acetate being more preferred.
[0199] There are no particular restrictions on the amount of the organic solvent used, and it can be appropriately selected depending on the purpose, but it is preferably 40 parts by mass or more and 300 parts by mass or less, more preferably 60 parts by mass or more and 140 parts by mass or less, and even more preferably 80 parts by mass or more and 120 parts by mass or less, per 100 parts by mass of the raw material for the resin particles.
[0200] There are no particular restrictions on the method for preparing the oil phase, and it can be appropriately selected depending on the purpose. For example, one method is to gradually add the materials for the oil phase to the organic solvent while stirring, and dissolve or disperse them. For the aforementioned dispersion, known methods can be used, such as dispersers like bead mills or disc mills.
[0201] <Aqueous phase (aqueous medium) production process> The aforementioned aqueous phase preparation step is a step of preparing an aqueous phase (aqueous medium). The aqueous medium is not particularly limited and can be appropriately selected depending on the purpose. Examples include water, a solvent miscible with water, or a mixture thereof. These may be used individually or in combination of two or more. Among these, water is preferred.
[0202] The water-miscible solvent is not particularly limited and can be appropriately selected according to the purpose, and examples thereof include alcohols, dimethylformamide, tetrahydrofuran, ethyl acetate, cellosolves, and lower ketones. The alcohol is not particularly limited and can be appropriately selected according to the purpose, and examples thereof include methanol, isopropanol, and ethylene glycol. The lower ketones are not particularly limited and can be appropriately selected according to the purpose, and examples thereof include acetone and methyl ethyl ketone.
[0203] <Phase inversion emulsification step> The phase inversion emulsification step is a step of adding an aqueous medium to the oil phase to invert the phase from a water-in-oil dispersion to an oil-in-water dispersion. Thereby, a fine particle dispersion (oil droplets) is obtained.
[0204] The method for subjecting the dispersion containing the amorphous polyester resin B to phase inversion emulsification in the aqueous medium is not particularly limited and can be appropriately selected according to the purpose, and examples thereof include a method of obtaining a fine particle dispersion by phase inversion emulsification, in which the oil phase is neutralized with a base or the like, then the aqueous phase is added thereto to invert the phase from a water-in-oil dispersion to an oil-in-water dispersion.
[0205] The method for subjecting the amorphous polyester resin A to phase inversion emulsification in the aqueous medium is not particularly limited and can be appropriately selected according to the purpose, and examples thereof include a method of obtaining a fine particle dispersion by phase inversion emulsification, in which the oil phase is neutralized with a base or the like, then the aqueous phase is added thereto to invert the phase from a water-in-oil dispersion to an oil-in-water dispersion.
[0206] Either a basic inorganic compound or a basic organic compound may be used as the base for neutralizing the oil phase. Examples of basic inorganic compounds include sodium hydroxide, potassium hydroxide, lithium hydroxide, ammonia, sodium carbonate, sodium bicarbonate, potassium carbonate, potassium bicarbonate, and ammonia. Examples of basic organic compounds include N,N-dimethylethanolamine, N,N-diethylethanolamine, triethanolamine, trippropanolamine, tributanolamine, triethylamine, n-propylamine, n-butylamine, isopropylamine, monomethanolamine, morpholine, methoxypropylamine, pyridine, vinylpyridine, and isophoronediamine.
[0207] Neutralization is carried out using a conventional stirrer or dispersion device to ensure uniform mixing and dispersion. There are no particular limitations on the dispersion device, but examples include ultrasonic dispersers, bead mills, ball mills, roll mills, homomixers, ultramixers, disper mixers, through-type high-pressure dispersion devices, impact-type high-pressure dispersion devices, porous high-pressure dispersion devices, ultra-high-pressure homogenizers, and ultrasonic homogenizers. A conventional stirrer and dispersion device may be used in combination.
[0208] There are no particular restrictions on the amount of the aqueous medium used when emulsifying the oil phase containing the resin particle material, and it can be appropriately selected according to the purpose. Preferably, the amount is 50 parts by mass or more and 2,000 parts by mass or less, and more preferably 100 parts by mass or more and 1,000 parts by mass or less, per 100 parts by mass of the resin particle material. If the amount of the aqueous medium used is 50 parts by mass or more per 100 parts by mass of the resin particle material, it is possible to prevent the dispersion state of the resin particle material from deteriorating and to suppress the inability to obtain resin particles of a predetermined particle size. Furthermore, if the amount of the aqueous medium used is 2,000 parts by mass or less per 100 parts by mass of the resin particle material, it is possible to suppress the increase in production costs.
[0209] When inverting and emulsifying the oil phase containing the aforementioned resin particle material, it is preferable to use a dispersant from the viewpoint of stabilizing dispersions such as oil droplets, giving them a desired shape, and sharpening the particle size distribution. There are no particular restrictions on the dispersant, and it can be appropriately selected depending on the purpose. Examples include surfactants, poorly water-soluble inorganic compound dispersants, or polymer-based protective colloids. These may be used individually or in combination of two or more. Among these, surfactants are preferred as the dispersant.
[0210] The surfactant is not particularly limited and can be appropriately selected depending on the purpose. Examples include anionic surfactants, cationic surfactants, nonionic surfactants, or amphoteric surfactants.
[0211] The anionic surfactant is not particularly limited and can be appropriately selected depending on the purpose. Examples include alkylbenzene sulfonates, α-olefin sulfonates, or phosphate esters. Among these, alkyl sulfates are preferred as the anionic surfactant.
[0212] The aforementioned phase inversion emulsification can be carried out using a stirring blade. The aforementioned stirring blades are not particularly limited and can be appropriately selected according to the viscosity of the solution. Examples include anchor blades, turbine blades, Faudler blades, full-zone blades, Maxblend blades, or crescent blades.
[0213] When using the aforementioned stirring blade, there are no particular restrictions on the peripheral speed, and it can be appropriately selected according to the purpose, but 0.4 m / sec to 2.0 m / sec is preferred, and 0.7 m / sec to 1.5 m / sec is more preferred.
[0214] There are no particular restrictions on the volume-average particle size of the dispersion (oil droplets) in the fine particle dispersion, and it can be appropriately selected depending on the purpose, but 50 nm to 2,000 nm is preferred, and 50 nm to 500 nm is more preferred.
[0215] <Solvent removal process> The solvent removal step is a step of removing the organic solvent from the fine particle dispersion obtained in the phase inversion emulsification step to obtain core particles.
[0216] There are no particular limitations on the method for removing the organic solvent from the fine particle dispersion, and a suitable method can be selected depending on the purpose. Examples include gradually raising the temperature of the entire reaction system to evaporate the organic solvent in the fine particle dispersion (oil droplets); spraying the fine particle dispersion into a dry atmosphere to remove the organic solvent; or reducing the pressure of the fine particle dispersion to evaporate and remove the organic solvent. These methods may be used individually or in combination of two or more.
[0217] There are no particular restrictions on the drying atmosphere in which the fine particle dispersion is sprayed, and it can be appropriately selected depending on the purpose. Examples include heated air, nitrogen, carbon dioxide, combustion gas, etc. In general, various gas streams heated to a temperature above the boiling point of the highest boiling point solvent used are used.
[0218] The solvent removal process can be carried out using equipment, such as a spray dryer, belt dryer, or rotary kiln, and the desired quality can be obtained in a short processing time.
[0219] <Agglomeration process> The aforementioned aggregation step is a step of agglomerating the particles of the oil-in-water dispersion to obtain aggregated particles. There are no particular limitations on the method for agglomerating the oil droplets or core particles, and a known method can be appropriately selected depending on the purpose. Examples include adding a flocculant or adjusting the pH.
[0220] There are no particular restrictions on the aforementioned flocculant, and it can be appropriately selected depending on the purpose. For example, aluminum chloride, zinc sulfate, magnesium sulfate, aluminum sulfate, potassium aluminum sulfate, sodium chloride, sodium bromide, sodium iodide, sodium fluoride, sodium acetate, sodium acetoacetate, lithium chloride, lithium bromide, lithium iodide, lithium fluoride, lithium acetate, lithium acetoacetate, potassium chloride, potassium bromide, potassium iodide, potassium fluoride, potassium acetoacetate, magnesium bromide, magnesium chloride, magnesium iodide, fluoride Examples include magnesium, magnesium acetate, magnesium acetoacetate, calcium chloride, calcium bromide, barium bromide, barium chloride, barium iodide, barium fluoride, barium acetate, barium acetoacetate, strontium bromide, strontium chloride, strontium iodide, strontium fluoride, strontium acetate, strontium acetoacetate, zinc bromide, zinc chloride, zinc iodide, zinc fluoride, zinc acetate, zinc acetoacetate, copper bromide, copper chloride, copper iodide, copper fluoride, copper acetate, copper acetoacetate, iron bromide, iron chloride, iron iodide, iron fluoride, iron acetate, or iron acetoacetate. These may be used individually or in combination of two or more. Among these, divalent metal salts are preferred as the flocculant, and trivalent metal salts are more preferred. By using a metal salt with a valency of 2 or higher, a three-dimensional structure can be formed by metal crosslinking with the carboxyl groups contained in the amorphous polyester resin A and the amorphous polyester resin B, thereby increasing the strength of the resin particles and improving their filming resistance.
[0221] When adding the aforementioned flocculant, it may be added as is, but it is preferable to use an aqueous solution of the flocculant to avoid localized high concentrations. Furthermore, it is preferable to add the flocculant gradually while observing the particle size of the resin particles.
[0222] The temperature of the reaction system in which the aggregation step is performed (the temperature of the dispersion liquid during aggregation) is not particularly limited and can be appropriately selected according to the purpose, but it is preferably near the glass transition temperature (Tg) of the amorphous polyester resin B. If the temperature is too low, aggregation may not proceed sufficiently, leading to poor efficiency, and if the temperature is too high, the aggregation rate increases, which may deteriorate the particle size distribution such as generation of coarse particles.
[0223] In the aggregation step, the aggregation is stopped after the aggregated particles reach the target particle size. The method for stopping the aggregation is not particularly limited and can be appropriately selected according to the purpose, and examples thereof include a method of adding a salt having a lower ionic valence than the aggregation salt or a chelating agent; a method of adjusting pH; a method of lowering the temperature of the reaction system (dispersion liquid) during aggregation; and a method of adding a large amount of an aqueous medium to dilute the concentration of the reaction system (dispersion liquid) during aggregation. These may be used alone or in combination of two or more thereof.
[0224] The volume average particle size of the aggregated particles is not particularly limited and can be appropriately selected according to the purpose, but is preferably 3.0 μm to 6.0 μm, and more preferably 4.0 μm to 5.0 μm.
[0225] In the aggregation step, a release agent may be added, and the crystalline resin may be added for low-temperature fixability. As the release agent, those described in the section of <<Release Agent>> can be used. As the crystalline resin, those described in the section of <<Crystalline Polyester Resin>> can be used. When the release agent or the crystalline resin is added in the aggregation step, a dispersion liquid in which the release agent is dispersed in an aqueous medium, or similarly a dispersion liquid of the crystalline polyester resin C is prepared, and the dispersion liquid is mixed with the fine particle dispersion liquid (oil droplets) and then aggregated, whereby aggregated particles in which the release agent and the crystalline resin are uniformly dispersed can be obtained.
[0226] There are no particular restrictions on the particle size of the release agent dispersed in the dispersion, and it can be appropriately selected depending on the purpose, but it is preferably 50 nm to 600 nm, and more preferably 50 nm to 300 nm. In this specification, the particle size of the release agent dispersed in the dispersion is the volume-average particle size.
[0227] There are no particular restrictions on the particle size of the crystalline resin dispersed in the dispersion, and it can be appropriately selected depending on the purpose, but it is preferably 50 nm to 600 nm, and more preferably 50 nm to 300 nm. In this specification, the particle size of the crystalline resin dispersed in the dispersion is the volume-average particle size.
[0228] The particle size of the release agent and the dispersed crystalline resin can be measured, for example, using a NanoTrac particle size distribution analyzer (UPA-EX150, Nikkiso Co., Ltd., dynamic light scattering method / laser Doppler method). The specific measurement method involves adjusting the dispersion containing the aforementioned release agent or crystalline resin to the measurement concentration range and then performing the measurement. Prior to this, a background measurement is performed using only the dispersion solvent of the dispersion. This method allows for measurements from several tens of nanometers to several micrometers.
[0229] <Shell layer formation process> Furthermore, it is preferable to add the polyester aqueous dispersion in the aggregation step in order to form a shell layer on the core particles. By forming a shell layer on the core particles, the crystalline resin and the release agent that would otherwise worsen the filming properties can be encapsulated, thereby improving filming resistance.
[0230] There are no particular limitations on the method for forming the shell layer, and it can be appropriately selected depending on the purpose. For example, one method is to produce aggregated particles by the method described above, and then add the polyester aqueous dispersion to the aggregated particles that have reached a desired particle size. Furthermore, if the method for producing the resin particles includes the solvent removal step, the polyester aqueous dispersion may be added after obtaining aggregated core particles in the solvent removal step.
[0231] <Fusing process> The fusion step is a process of fusing the aggregated particles to reduce irregularities and obtain spherical resin particles. Furthermore, if resin is added in the aggregation step to form a shell layer on the resin particles, the fusion step can form a shell layer on the surface of the aggregated particles.
[0232] There are no particular limitations on the method for fusing the aggregated particles, and a suitable method can be selected depending on the purpose. For example, a method of heating the dispersion of the aggregated particles while stirring can be used.
[0233] There are no particular restrictions on the heating temperature, and it can be appropriately selected depending on the purpose, but it is preferably between Tg and Tg+20°C of the amorphous polyester resin B, and more preferably between Tg and Tg+10°C. When the heating temperature is below Tg+20°C of the amorphous polyester resin B, the amorphous polyester resin B and the crystalline resin C become appropriately compatible, improving heat resistance and storage properties.
[0234] There are no particular restrictions on the average circularity of the resin particles, and they can be appropriately selected depending on the purpose. However, a higher average circularity of the resin particles is preferable, as it allows them to rotate more smoothly in the developing nip when used as toner, thus enabling more resin particles to transfer to the electrostatic latent image carrier. In this respect, a circularity of 0.95 or higher is preferable, and 0.96 or higher is more preferable.
[0235] -Measuring average circularity- In this embodiment, the average particle diameter and average circularity can be measured, for example, using a flow-type particle image analyzer (FPIA-3000, manufactured by Sysmex Corporation). The specific measurement method involves adding 0.1 mL to 0.5 mL of a surfactant, preferably alkylbenzene sulfonate, as a dispersant to 100 mL to 150 mL of water from which impurities have been removed beforehand, and then adding approximately 0.1 g to 0.5 g of the sample to be measured. The suspension in which the sample is dispersed is subjected to dispersion treatment in an ultrasonic disperser for approximately 1 to 3 minutes, and the dispersion concentration is set to 3,000 particles / μL to 10,000 particles / μL. The average particle size, average circularity, and standard deviation (SD) of circularity are then measured using the aforementioned apparatus. However, the particle diameter shall be the equivalent diameter of a circle, the average particle diameter shall be determined by the equivalent diameter of a circle (based on the number of particles), and the analysis conditions for the flow-type particle image analyzer shall be as follows. [Analysis conditions] Particle size limit: 0.5 μm ≤ Equivalent circle diameter (based on number of particles) ≤ 200.0 μm Particle shape limitation: 0.93 < Circularity ≤ 1.00 Furthermore, in this embodiment, the definition of average circularity is as follows: (Average circularity) = (Perimeter of a circle equal to the projected area of the particle) / (Perimeter of the projected image of the particle)
[0236] <Washing Process> The washing step is a step of washing the resin particles obtained in the aggregation step or the fusion step. Since the dispersion of resin particles obtained by the method described above may contain auxiliary materials such as flocculants in addition to the resin particles, it is preferable to wash the dispersion to separate only the resin particles.
[0237] There are no particular restrictions on the method for washing the resin particles, and it can be appropriately selected depending on the purpose. Examples include centrifugal separation, vacuum filtration, or filter pressing. A cake of resin particles can be obtained by any of the washing methods, but if the cake cannot be sufficiently washed in one operation, the obtained cake may be dispersed again in an aqueous solvent to form a slurry, and the process of extracting the resin particles may be repeated using at least one of the washing methods. When washing is performed by the vacuum filtration method or the filter press method, a method may be used in which an aqueous solvent is passed through the cake body to wash away the auxiliary materials that the resin particles have incorporated.
[0238] The aqueous solvent used in the cleaning step is not particularly limited and can be appropriately selected depending on the purpose. Examples include water or a mixed solvent of water and alcohol. Examples of the alcohol include methanol or ethanol. Among these, water is preferred as the aqueous solvent due to its cost and environmental impact from wastewater treatment.
[0239] <Drying process> The drying step is a step of washing the resin particles obtained in the washing step. Since the resin particles washed in the washing step contain a large amount of the aqueous medium, drying them in the drying step removes the aqueous medium, allowing only the resin particles to be obtained.
[0240] There are no particular restrictions on the drying method, and it can be appropriately selected according to the purpose. Examples include using a spray dryer, vacuum freeze dryer, reduced pressure dryer, stationary shelf dryer, mobile shelf dryer, fluidized bed dryer, rotary dryer, or agitated dryer.
[0241] There are no particular restrictions on the final moisture content of the dried resin particles, and it can be appropriately selected depending on the purpose, but it is preferable that the moisture content is less than 1% by mass.
[0242] The resin particles dried in the aforementioned drying process are soft and aggregated. If this causes problems during use, they may be crushed to break up the aggregates. There are no particular restrictions on the method of crushing, and it can be appropriately selected depending on the purpose. Examples include using a jet mill, Henschel mixer, super mixer, coffee mill, Auster blender, or food processor.
[0243] <Classification process> The classification process is a process of classifying the resin particles obtained in the washing process or the drying process. There are no particular restrictions on the classification method, and it can be appropriately selected depending on the purpose. Examples include methods that remove fine particles in a liquid using a cyclone, decanter, centrifugation, etc., or methods that perform known classification operations after drying.
[0244] <Annealing Process> The annealing step is performed after the drying step when a crystalline resin is added, and is a step that separates the crystalline resin from the amorphous polyester resin.
[0245] There are no particular restrictions on the method of performing the annealing treatment, and it can be appropriately selected depending on the purpose, but examples include storing the crystalline resin at a temperature near its glass transition temperature (Tg) for 10 hours or more.
[0246] In the aforementioned fusion process, if the material is heated to a temperature near the glass transition temperature (Tg) of the resin being used, the crystalline resin and the amorphous polyester resin may become miscible, making it impossible to achieve both heat resistance and low-temperature fixation. However, the annealing treatment is advantageous because it promotes phase separation between the crystalline resin and the amorphous resin, eliminating the miscible state.
[0247] (toner) The toner of the present invention preferably contains the resin particles for toner of the present invention, and further contains an external additive, and may contain other components as needed.
[0248] <Resin particles for toner> The resin particles constituting the aforementioned toner resin particles are as described in the sections (Resin Particles) and (Toner Resin Particles), and their details are omitted. In the aforementioned toner, the resin particles for the toner become toner matrix particles.
[0249] There are no particular restrictions on the content of the toner resin particles in the toner, and it can be appropriately selected depending on the purpose. The toner may also be the toner resin particles themselves.
[0250] <External additives> There are no particular restrictions on the external additives, and they can be appropriately selected depending on the purpose. Examples include inorganic fine particles, oxide fine particles, fatty acid metal salts, or hydrophobized versions thereof. These may be used individually or in combination of two or more.
[0251] There are no particular restrictions on the average particle size of the primary particles of the inorganic fine particles, and it can be appropriately selected depending on the purpose, but it is preferably 100 nm or less, more preferably 1 nm to 100 nm, even more preferably 3 nm to 70 nm, and particularly preferably 5 nm to 70 nm. If the average particle size of the primary particles of the inorganic fine particles is 1 nm or more, it is possible to prevent the inorganic fine particles from becoming embedded in the toner and not being able to effectively perform their function, and if it is 100 nm or less, it is possible to suppress uneven scratching of the photoreceptor surface.
[0252] Furthermore, it is preferable that the inorganic fine particles include at least one type of inorganic fine particles having an average primary particle size of 20 nm or less, and at least one type of inorganic fine particles having an average primary particle size of 30 nm or more.
[0253] There are no particular restrictions on the specific surface area of the inorganic fine particles obtained by the BET method, and it can be appropriately selected depending on the purpose, but 20m 2 / g or more 500m 2 It is preferable that the value be less than or equal to / g.
[0254] The inorganic fine particles are not particularly limited and can be appropriately selected depending on the purpose. Examples include silica, alumina, titanium oxide, barium titanate, magnesium titanate, calcium titanate, strontium titanate, iron oxide, copper oxide, zinc oxide, tin oxide, silica sand, clay, mica, wollastonite, diatomaceous earth, chromium oxide, cerium oxide, red iron oxide, antimony trioxide, magnesium oxide, zirconium oxide, barium sulfate, barium carbonate, calcium carbonate, silicon carbide, or silicon nitride. These may be used individually or in combination of two or more. Among these, silica or titanium dioxide are preferred.
[0255] The oxide fine particles are not particularly limited and can be appropriately selected depending on the purpose. Examples include titania, alumina, tin oxide, or antimony oxide.
[0256] Examples of the fatty acid metal salt include zinc stearate or aluminum stearate.
[0257] Among these, hydrophobized silica, titania, titanium dioxide, or alumina fine particles are preferred as the external additive.
[0258] Examples of the silica nanoparticles mentioned above include R972, R974, RX200, RY200, R202, R805, or R812 (all manufactured by Nippon Aerosil Co., Ltd.).
[0259] Examples of the titania particles include P-25 (manufactured by Nippon Aerosil Co., Ltd.), STT-30, STT-65C-S (all manufactured by Titanium Industry Co., Ltd.), TAF-140 (manufactured by Fuji Titanium Industry Co., Ltd.), MT-150W, MT-500B, MT-600B, or MT-150A (all manufactured by Teika Co., Ltd.).
[0260] Examples of the hydrophobized titanium oxide nanoparticles include T-805 (manufactured by Nippon Aerosil Co., Ltd.), STT-30A, STT-65S-S (all manufactured by Titanium Industry Co., Ltd.), TAF-500T, TAF-1500T (both manufactured by Fuji Titanium Industry Co., Ltd.), MT-100S, MT-100T (both manufactured by Teika Co., Ltd.), or IT-S (manufactured by Ishihara Sangyo Co., Ltd.).
[0261] The hydrophobized oxide nanoparticles, hydrophobized silica nanoparticles, hydrophobized titania nanoparticles, or hydrophobized alumina nanoparticles can be obtained, for example, by treating hydrophilic nanoparticles with a silane coupling agent such as methyltrimethoxysilane, methyltriethoxysilane, or octyltrimethoxysilane. Silicone oil-treated oxide nanoparticles and inorganic nanoparticles obtained by treating silicone oil with heat if necessary are also suitable. Furthermore, the external additives can also be surface-treated with the aforementioned fluidity improvers.
[0262] The silicone oil is not particularly limited and can be appropriately selected depending on the purpose. Examples include dimethyl silicone oil, methylphenyl silicone oil, chlorophenyl silicone oil, methyl hydrogen silicone oil, alkyl-modified silicone oil, fluorine-modified silicone oil, polyether-modified silicone oil, alcohol-modified silicone oil, amino-modified silicone oil, epoxy-modified silicone oil, epoxy-polyether-modified silicone oil, phenol-modified silicone oil, carboxyl-modified silicone oil, mercapto-modified silicone oil, methacrylic-modified silicone oil, or α-methylstyrene-modified silicone oil.
[0263] There are no particular restrictions on the content of the external additive, and it can be appropriately selected depending on the purpose, but it is preferably 0.1 parts by mass or more and 5 parts by mass or less, and more preferably 0.3 parts by mass or more and 3 parts by mass or less, per 100 parts by mass of toner.
[0264] There are no particular restrictions on the method for manufacturing the toner, and any known method can be appropriately selected; however, it is preferable that the toner be manufactured by the method for manufacturing toner of the present invention, which will be described later.
[0265] (Toner manufacturing method) The toner manufacturing method of the present invention includes a mixing step of mixing the toner resin particles of the present invention with an external additive, and further includes other steps as necessary.
[0266] The resin particles for the toner are as described in the sections (Resin Particles) and (Resin Particles for Toner), and the external additives are as described in the section (External Additives) of (Toner), and their details are omitted.
[0267] <Mixing process> The mixing step involves mixing the toner resin particles, which serve as the toner matrix particles, with the external additive. Applying a mechanical impact force at this stage is preferable because it can suppress the detachment of the external additive particles from the surface of the toner matrix particles.
[0268] There are no particular limitations on the method of applying the mechanical impact force, and it can be appropriately selected depending on the purpose. Examples include a method of applying impact force to the mixture of the toner resin particles and the external additive using a blade that rotates at high speed; and a method of introducing the mixture of the toner resin particles and the external additive into a high-speed airflow, accelerating it, and causing the particles to collide with each other or with a suitable impact plate.
[0269] There are no particular restrictions on the devices used in the method of applying the aforementioned mechanical impact force, and they can be appropriately selected according to the purpose. Examples include an Ongmill (manufactured by Hosokawa Micron Corporation), a modified I-type mill (manufactured by Nippon Pneumatic Mfg. Co., Ltd.) with reduced grinding air pressure, a hybridization system (manufactured by Nara Machinery Works Co., Ltd.), a cryptron system (manufactured by Kawasaki Heavy Industries, Ltd.), and an automatic mortar and pestle.
[0270] <Other ingredients> The aforementioned other components are not particularly limited and can be selected as needed. Examples include antifoaming agents, pH adjusters, preservatives and antifungal agents, chelating agents, rust inhibitors, antioxidants, ultraviolet absorbers, oxygen absorbers, or light stabilizers. These may be used individually or in combination of two or more.
[0271] The content of the other components in the ink is not particularly limited, as long as it does not impair the effects of the present invention, and can be appropriately selected depending on the purpose.
[0272] (Developer) The developer of the present invention contains at least the toner of the present invention, and further contains other components that are appropriately selected, such as a carrier, as needed. The toner contained in the developer of the present invention contains the resin particles for toner of the present invention, and therefore the developer is environmentally friendly and has excellent electrostatic stability, low-temperature fixing properties, and heat-resistant storage properties. For this reason, the developer has excellent transferability, electrostatic properties, etc., and can stably form high-quality images.
[0273] The developer may be a one-component developer or a two-component developer, but when used in high-speed printers and the like to accommodate the recent increase in information processing speed, a two-component developer is preferred because it extends the lifespan.
[0274] When the developer is used as a single-component developer, even when the toner is balanced, there is little variation in the particle size of the toner, resulting in less toner filming onto the developing roller and less toner fusion onto components such as blades that thin the toner layer. This allows for good and stable development and image quality even during long-term agitation in the developing apparatus.
[0275] When the aforementioned developer is used as a two-component developer, even with long-term toner balance, there is little variation in toner particle size, and good and stable developability and images can be obtained even with long-term agitation in the developing device.
[0276] <Career> There are no particular restrictions on the carrier, and it can be appropriately selected according to the purpose, but one having a core material and a resin layer covering the core material is preferred.
[0277] <<Core material>> There are no particular restrictions on the core material, and it can be appropriately selected according to the purpose. For example, manganese-strontium materials with a magnetization of 50 emu / g to 90 emu / g, or manganese-magnesium materials with a magnetization of 50 emu / g to 90 emu / g are available. Furthermore, in order to ensure image density, it is preferable to use highly magnetized materials such as iron powder of 100 emu / g or more, or magnetite with a magnetization of 75 emu / g to 120 emu / g. In addition, it is preferable to use low magnetized materials such as copper-zinc materials with a magnetization of 30 emu / g to 80 emu / g, as this can mitigate the impact of the developer in a slushy state on the photoreceptor and is advantageous for improving image quality. These can be used individually or in combination of two or more.
[0278] There are no particular restrictions on the volume-average particle diameter of the core material, and it can be appropriately selected according to the purpose, but it is preferably 10 μm to 150 μm, and more preferably 40 μm to 100 μm. When the volume-average particle diameter of the core material is 10 μm or more, it is possible to prevent a large amount of fine powder from accumulating in the carrier, and to suppress the decrease in magnetization per particle and the resulting scattering of carriers. Furthermore, when the volume-average particle diameter of the core material is 150 μm or less, it is possible to prevent a decrease in specific surface area and to suppress the scattering of toner, and in full-color printing with many solid areas, it is possible to suppress the deterioration of reproduction of solid areas in particular.
[0279] When the toner is used in a two-component developer, it may be used in combination with the carrier. There are no particular restrictions on the amount of the carrier in the two-component developer, and it can be appropriately selected depending on the purpose, but it is preferably 90 parts by mass or more and 98 parts by mass or less, and more preferably 93 parts by mass or more and 97 parts by mass or less, per 100 parts by mass of the two-component developer.
[0280] The developer can be suitably used for image formation by various known electrophotographic methods, including magnetic one-component development methods, non-magnetic one-component development methods, or two-component development methods. Alternatively, a premix development method may be adopted, in which a premix developer containing toner and carrier is supplied. In the premix development method, the excess amount of carrier in the developing unit is discharged as excess developer. This gradually refreshes the developer in the developing unit. Therefore, it is possible to extend the replacement cycle due to developer deterioration and reduce the effort required to replace the developer.
[0281] (Image forming apparatus and image forming method) The image forming apparatus of the present invention comprises an electrostatic latent image carrier, an electrostatic latent image forming means for forming an electrostatic latent image on the electrostatic latent image carrier, and a developing means comprising a toner for developing the electrostatic latent image formed on the electrostatic latent image carrier to form a visible image, and further comprises other means as necessary. The toner in the developing means is the toner of the present invention.
[0282] (Image forming apparatus) Next, one embodiment of the method for forming an image using the image forming apparatus of the present invention will be described with reference to Figure 1. In this embodiment, a printer is shown as an example of the image forming apparatus, but the image forming apparatus is not particularly limited as long as it is capable of forming an image using toner, such as a copier, facsimile, or multifunction device. The image forming apparatus 200 includes a paper feeding unit 210, a transport unit 220, an image forming unit 230, a transfer unit 240, and a fuser unit 250. The paper feeding unit 210 includes a paper feed cassette 211 on which the paper to be fed P is stacked, and a paper feed roller 212 that feeds the paper P from the paper feed cassette 211 one sheet at a time.
[0283] The transport unit 220 includes a roller 221 that transports the paper P fed by the paper feed roller 212 toward the transfer unit 240, a pair of timing rollers 222 that hold the leading edge of the paper P transported by the roller 221 and wait, and send the paper to the transfer unit 240 at a predetermined timing, and a paper discharge roller 223 that discharges the paper P on which the color toner image has been fixed toward the paper discharge tray 224.
[0284] The image-forming unit 230 comprises, at predetermined intervals and arranged sequentially from left to right in the figure, an image-forming unit 180Y that forms an image using a developer containing yellow toner, an image-forming unit 180C that uses a developer containing cyan toner, an image-forming unit 180M that uses a developer containing magenta toner, an image-forming unit 180K that uses a developer containing black toner, chargers 232Y, 232C, 232M, 232K, and an exposure unit 233. The exposure unit 233 has a light source 233a and polygon mirrors 233bY, 233bC, 233bM, 233bK. It also has toner bottles 234Y, 234M, 234C, 234K, sub-hoppers 160Y, 160M, 160C, 160K, and cleaning units 236Y, 236M, 236C, 236K. Furthermore, when referring to any of the image forming units (Y, C, M, K), the term "image forming unit" is used.
[0285] Furthermore, the developer contains toner and carrier. The four image forming units (Y, C, M, K) are virtually identical in their mechanical configuration, differing only in the developer they use.
[0286] The transfer unit 240 includes a drive roller 241 and a driven roller 242, an intermediate transfer belt 243 that can rotate counterclockwise in the figure as the drive roller 241 is driven, primary transfer rollers (244Y, 244C, 244M, 244K) provided opposite to the photoreceptor drums 231Y, 231C, 231M, and 231K respectively, with the intermediate transfer belt 243 in between, and secondary opposing rollers 245 and secondary transfer rollers 246 provided opposite to the intermediate transfer belt 243 at the position where the toner image is transferred to the paper.
[0287] The fuser unit 250 has a heater inside and includes a fuser belt 251 that heats the paper P, and a pressure roller 252 that rotatably applies pressure to the fuser belt 251 to form a nip. As a result, heat and pressure are applied to the color toner image on the paper P, fixing the color toner image. The paper P with the fixed color toner image is ejected to the paper output tray 224 by the paper output roller 223, completing the image forming process.
[0288] (Developer storage unit) In this invention, a developer-containing unit refers to a unit that contains a developer within a unit having the function of containing a developer. Here, the forms of the developer storage unit include a container for developer, a developer unit, and a process cartridge. A container containing developer refers to a container that holds the developer. A developing unit refers to a device that contains a developer and has the means to develop the film. A process cartridge refers to a device that integrates at least an image carrier and a developing means, and is detachable from an image forming apparatus. At least one of a charging means, an exposure means, and a cleaning means may be integrated with the image carrier and the developing means.
[0289] (Processing cartridge) The process cartridge according to the present invention is molded to be detachably attached to various image forming apparatuses and comprises at least an electrostatic latent image carrier that carries an electrostatic latent image, and a developing means that develops the electrostatic latent image carried on the electrostatic latent image carrier with the developer of the present invention to form a toner image. The process cartridge may further comprise other means as needed.
[0290] The developing means includes at least a developer storage section for containing the developer of the present invention, and a developer carrier for carrying and transporting the developer contained in the developer storage section. The developing means may further include a regulating member or the like to regulate the thickness of the carried developer.
[0291] Figure 2 shows an example of a process cartridge according to the present invention. The process cartridge 110 includes a photoreceptor drum 10, a corona charger 58, a developer 40, a transfer roller 80, and a cleaning device 90. L is laser light, and 95 is paper P. [Examples]
[0292] The present invention will be specifically described below with reference to manufacturing examples, examples, and comparative examples, but the present invention is not limited in any way to these manufacturing examples, preparation examples, and examples. In the manufacturing examples, preparation examples, examples, and comparative examples, unless otherwise specified, "%" refers to "mass%" and "parts" refers to "parts by mass". In addition, the blending amounts in the examples and comparative examples indicate the blending amount of solids in each raw material.
[0293] (Manufacturing example A-1: Synthesis of amorphous polyester resin A-1) In a four-necked flask equipped with a nitrogen inlet tube, dehydration tube, stirrer, and thermocouple, 497 parts of bisphenol A propylene oxide 2 molar adduct (manufactured by Sanyo Chemical Industries, Ltd.), 111 parts of recycled PBT (manufactured by Intertek Co., Ltd.), 300 parts of plant-derived dodecanedioic acid (manufactured by Tokyo Chemical Industries, Ltd.), and 91 parts of sodium 5-sulfoisophthalate (manufactured by Tokyo Chemical Industries, Ltd.) were charged. The mixture was then reacted with titanium tetraisopropoxide (500 ppm relative to the resin component) at atmospheric pressure and 230°C for 8 hours, followed by a further reaction under reduced pressure of 10 mmHg to 15 mmHg for 4 hours. After that, 5 parts of trimellitic anhydride were added to the reaction vessel, and the mixture was reacted at 180°C and atmospheric pressure for 3 hours to obtain [amorphous polyester resin A-1]. The composition and physical properties of this resin are shown in Tables 1 and 2 below.
[0294] (Manufacturing Example A-2: Synthesis of Amorphous Polyester Resin A-2) In a four-necked flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple, 282 parts of bisphenol A ethylene oxide 2 molar adduct (manufactured by Sanyo Chemical Industries, Ltd.), 297 parts of bisphenol A propylene oxide 2 molar adduct (manufactured by Sanyo Chemical Industries, Ltd.), 303 parts of adipic acid (manufactured by Hayashi Pure Chemical Industries, Ltd.), and 118 parts of recycled PET (manufactured by Kyoei J&T Environmental Co., Ltd.) were charged. These were reacted with titanium tetraisopropoxide (500 ppm relative to the resin component) at atmospheric pressure and 230°C for 8 hours, and then further reacted under reduced pressure of 10 mmHg to 15 mmHg for 4 hours. After that, 5 parts of trimellitic anhydride were added to the reaction vessel and reacted at 180°C and atmospheric pressure for 3 hours to obtain [amorphous polyester resin A-2]. The composition and physical properties of this resin are shown in Tables 1 and 2 below.
[0295] (Manufacturing Example A-3: Synthesis of Amorphous Polyester Resin A-3) In a four-necked flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple, 576 parts of bisphenol A propylene oxide 2 molar adduct (manufactured by Sanyo Chemical Industries, Ltd.), 294 parts of adipic acid (manufactured by Hayashi Pure Chemical Industries, Ltd.), and 129 parts of recycled PET (manufactured by Kyoei J&T Environmental Co., Ltd.) were charged. These were reacted with titanium tetraisopropoxide (500 ppm relative to the resin component) at atmospheric pressure and 230°C for 8 hours, and then further reacted under reduced pressure of 10 mmHg to 15 mmHg for 4 hours. After that, 5 parts of trimellitic anhydride were added to the reaction vessel and reacted at 180°C and atmospheric pressure for 3 hours to obtain [amorphous polyester resin A-3]. The composition and physical properties of this resin are shown in Tables 1 and 2 below.
[0296] (Manufacturing example A-4: Synthesis of amorphous polyester resin A-4) In a four-necked flask equipped with a nitrogen inlet tube, dehydration tube, stirrer, and thermocouple, 499 parts of bisphenol A propylene oxide 2 molar adduct (manufactured by Sanyo Chemical Industries, Ltd.), 401 parts of plant-derived dodecanedioic acid (manufactured by Tokyo Chemical Industries, Ltd.), and 99 parts of recycled PET (manufactured by Kyoei J&T Environmental Co., Ltd.) were charged. These were reacted with titanium tetraisopropoxide (500 ppm relative to the resin component) at atmospheric pressure and 230°C for 8 hours, and then further reacted under reduced pressure of 10 mmHg to 15 mmHg for 4 hours. After that, 5 parts of trimellitic anhydride were added to the reaction vessel and reacted at 180°C and atmospheric pressure for 3 hours to obtain [amorphous polyester resin A-4]. The composition and physical properties of this resin are shown in Tables 1 and 2 below.
[0297] (Manufacturing example A-5: Synthesis of amorphous polyester resin A-5) In a four-necked flask equipped with a nitrogen inlet tube, dehydration tube, stirrer, and thermocouple, 592 parts of bisphenol A propylene oxide 2 molar adduct (manufactured by Sanyo Chemical Industries, Ltd.), 242 parts of adipic acid (manufactured by Hayashi Pure Chemical Industries, Ltd.), 49 parts of plant-derived succinic acid (manufactured by Tokyo Chemical Industries, Ltd.), and 118 parts of recycled PET (manufactured by Kyoei J&T Environmental Co., Ltd.) were charged. The mixture was reacted with titanium tetraisopropoxide (500 ppm relative to the resin component) at atmospheric pressure and 230°C for 8 hours, followed by a further reaction under reduced pressure of 10 mmHg to 15 mmHg for 4 hours. After that, 5 parts of trimellitic anhydride were added to the reaction vessel and the mixture was reacted at 180°C and atmospheric pressure for 3 hours to obtain [amorphous polyester resin A-5]. The composition and physical properties of this resin are shown in Tables 1 and 2 below.
[0298] (Manufacturing example A-6: Synthesis of amorphous polyester resin A-6) In a four-necked flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple, 549 parts of 2 molar bisphenol A propylene oxide adduct (manufactured by Sanyo Chemical Industries, Ltd.), 280 parts of adipic acid (manufactured by Hayashi Pure Chemical Industries, Ltd.), and 170 parts of recycled PET (manufactured by Kyoei J&T Environmental Co., Ltd.) were charged. These were reacted with titanium tetraisopropoxide (500 ppm relative to the resin component) at atmospheric pressure and 230°C for 8 hours, and then further reacted under reduced pressure of 10 mmHg to 15 mmHg for 4 hours. After that, 5 parts of trimellitic anhydride were added to the reaction vessel and reacted at 180°C and atmospheric pressure for 3 hours to obtain [amorphous polyester resin A-6]. The composition and physical properties of this resin are shown in Tables 1 and 2 below.
[0299] (Manufacturing example A-7: Synthesis of amorphous polyester resin A-7) In a four-necked flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple, 254 parts of bisphenol A ethylene oxide 2 molar adduct (manufactured by Sanyo Chemical Industries, Ltd.), 268 parts of bisphenol A propylene oxide 2 molar adduct (manufactured by Sanyo Chemical Industries, Ltd.), 102 parts of adipic acid (manufactured by Hayashi Pure Chemical Industries, Ltd.), 107 parts of recycled PET (manufactured by Kyoei J&T Environmental Co., Ltd.), and 269 parts of plant-derived dodecanediic acid (manufactured by Tokyo Chemical Industries, Ltd.) were charged. These were reacted with titanium tetraisopropoxide (500 ppm relative to the resin component) at atmospheric pressure and 230°C for 8 hours, and then reacted again for 4 hours under reduced pressure of 10 mmHg to 15 mmHg. After that, 5 parts of trimellitic anhydride were added to the reaction vessel and reacted at 180°C and atmospheric pressure for 3 hours to obtain [amorphous polyester resin A-7]. The composition and physical properties of this resin are shown in Tables 1 and 2 below.
[0300] (Manufacturing example A-8: Synthesis of amorphous polyester resin A-8) In a four-necked flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple, 376 parts of bisphenol A ethylene oxide 2 molar adduct (manufactured by Sanyo Chemical Industries, Ltd.), 264 parts of bisphenol A propylene oxide 2 molar adduct (manufactured by Sanyo Chemical Industries, Ltd.), 168 parts of adipic acid (manufactured by Hayashi Pure Chemical Industries, Ltd.), and 191 parts of terephthalic acid (manufactured by Toray Industries, Inc.) were charged. These were reacted with titanium tetraisopropoxide (500 ppm relative to the resin component) at atmospheric pressure and 230°C for 8 hours, followed by a further reaction under reduced pressure of 10 mmHg to 15 mmHg for 4 hours. Then, 5 parts of trimellitic anhydride were added to the reaction vessel, and the mixture was reacted at 180°C and atmospheric pressure for 3 hours to obtain [amorphous polyester resin A-8]. The composition and physical properties of this resin are shown in Tables 1 and 2 below.
[0301] (Manufacturing example A-9: Synthesis of amorphous polyester resin A-9) In a four-necked flask equipped with a nitrogen inlet tube, dehydration tube, stirrer, and thermocouple, 45 parts of plant-derived 1,3-butanediol (manufactured by Daicel Corporation), 31 parts of plant-derived ethylene glycol, 429 parts of bisphenol A propylene oxide 2 molar adduct (manufactured by Sanyo Chemical Industries, Ltd.), 207 parts of plant-derived terephthalic acid (manufactured by Idemitsu Kosan Co., Ltd.), and 288 parts of plant-derived dodecanediic acid (manufactured by Tokyo Chemical Industries, Ltd.) were charged. These were reacted with titanium tetraisopropoxide (500 ppm relative to the resin component) at atmospheric pressure and 230°C for 8 hours, and then further reacted under reduced pressure of 10 mmHg to 15 mmHg for 4 hours. After that, 5 parts of trimellitic anhydride were added to the reaction vessel and reacted at 180°C and atmospheric pressure for 3 hours to obtain [amorphous polyester resin A-9]. The composition and physical properties of this resin are shown in Table 1 below. Table 2 also shows the weight-average molecular weight and glass transition temperature (Tg) of each resin.
[0302] [Table 1]
[0303] [Table 2]
[0304] (Manufacturing example B-1: Synthesis of amorphous polyester resin B-1) In a four-necked flask equipped with a nitrogen inlet tube, dehydration tube, stirrer, and thermocouple, 45 parts of plant-derived 1,3-butanediol (manufactured by Daicel Corporation), 31 parts of plant-derived ethylene glycol, 429 parts of bisphenol A propylene oxide 2 molar adduct (manufactured by Sanyo Chemical Industries, Ltd.), 207 parts of plant-derived terephthalic acid (manufactured by Idemitsu Kosan Co., Ltd.), and 288 parts of plant-derived dodecanediic acid (manufactured by Tokyo Chemical Industries, Ltd.) were charged. These were reacted with titanium tetraisopropoxide (500 ppm relative to the resin component) at atmospheric pressure and 230°C for 10 hours, and then further reacted under reduced pressure of 10 mmHg to 15 mmHg for 6 hours. After that, 5 parts of trimellitic anhydride were added to the reaction vessel and reacted at 180°C and atmospheric pressure for 3 hours to obtain [amorphous polyester resin B-1]. The composition and physical properties of this resin are shown in Tables 3 and 4 below.
[0305] (Manufacturing Example B-2: Synthesis of Amorphous Polyester Resin B-2) In a four-necked flask equipped with a nitrogen inlet tube, dehydration tube, stirrer, and thermocouple, 458 parts of 2 molar bisphenol A propylene oxide adduct (manufactured by Sanyo Chemical Industries, Ltd.), 316 parts of plant-derived dodecanedioic acid (manufactured by Tokyo Chemical Industries, Ltd.), 69 parts of plant-derived abietic acid (manufactured by Tokyo Chemical Industries, Ltd.), and 157 parts of recycled PET (manufactured by Kyoei J&T Environmental Co., Ltd.) were charged. The mixture was reacted with titanium tetraisopropoxide (500 ppm relative to the resin component) at atmospheric pressure and 230°C for 10 hours, followed by a further reaction under reduced pressure of 10 mmHg to 15 mmHg for 6 hours. After that, 5 parts of trimellitic anhydride were added to the reaction vessel and the mixture was reacted at 180°C and atmospheric pressure for 3 hours to obtain [amorphous polyester resin B-2]. The composition and physical properties of this resin are shown in Tables 3 and 4 below.
[0306] (Manufacturing Example B-3: Synthesis of Amorphous Polyester Resin B-3) In a four-necked flask equipped with a nitrogen inlet tube, dehydration tube, stirrer, and thermocouple, 557 parts of bisphenol A ethylene oxide 2 molar adduct (manufactured by Sanyo Chemical Industries, Ltd.), 146 parts of bisphenol A propylene oxide 2 molar adduct (manufactured by Sanyo Chemical Industries, Ltd.), 85 parts of isophthalic acid (manufactured by Mitsubishi Gas Chemical Company, Ltd.), and 212 parts of terephthalic acid (manufactured by Toray Industries, Inc.) were charged. These were reacted with titanium tetraisopropoxide (500 ppm relative to the resin component) at atmospheric pressure and 230°C for 10 hours, followed by a further reaction under reduced pressure of 10 mmHg to 15 mmHg for 6 hours. After that, 5 parts of trimellitic anhydride were added to the reaction vessel and the mixture was reacted at 180°C and atmospheric pressure for 3 hours to obtain [amorphous polyester resin B-3]. The composition and physical properties of this resin are shown in Tables 3 and 4 below.
[0307] (Manufacturing example B-4: Synthesis of amorphous polyester resin B-4) In a four-necked flask equipped with a nitrogen inlet tube, dehydration tube, stirrer, and thermocouple, 497 parts of bisphenol A propylene oxide 2 molar adduct (manufactured by Sanyo Chemical Industries, Ltd.), 111 parts of recycled PBT (manufactured by Intertek Co., Ltd.), 300 parts of plant-derived dodecanedioic acid (manufactured by Tokyo Chemical Industries, Ltd.), and 91 parts of sodium 5-sulfoisophthalate (manufactured by Tokyo Chemical Industries, Ltd.) were charged. This mixture was then reacted with titanium tetraisopropoxide (500 ppm relative to the resin component) at atmospheric pressure and 230°C for 10 hours, followed by a further reaction under reduced pressure of 10 mmHg to 15 mmHg for 6 hours. Finally, 5 parts of trimellitic anhydride were added to the reaction vessel, and the mixture was reacted at 180°C and atmospheric pressure for 3 hours to obtain [amorphous polyester resin B-4]. The composition and physical properties of this resin are shown in Tables 3 and 4 below.
[0308] (Manufacturing example B-5: Synthesis of amorphous polyester resin B-5) In a four-necked flask equipped with a nitrogen inlet tube, dehydration tube, stirrer, and thermocouple, 327 parts of bisphenol A ethylene oxide 2 molar adduct (manufactured by Sanyo Chemical Industries, Ltd.), 344 parts of bisphenol A propylene oxide 2 molar adduct (manufactured by Sanyo Chemical Industries, Ltd.), 80 parts of isophthalic acid (manufactured by Mitsubishi Gas Chemical Company, Ltd.), 80 parts of terephthalic acid (manufactured by Toray Industries, Inc.), and 170 parts of plant-derived succinic acid (manufactured by Tokyo Chemical Industries, Ltd.) were charged. These were reacted with titanium tetraisopropoxide (500 ppm relative to the resin component) at atmospheric pressure and 230°C for 10 hours, and then reacted again for 6 hours under reduced pressure of 10 mmHg to 15 mmHg. After that, 5 parts of trimellitic anhydride were added to the reaction vessel and reacted at 180°C and atmospheric pressure for 3 hours to obtain [amorphous polyester resin B-5]. The composition and physical properties of this resin are shown in Tables 3 and 4 below.
[0309] (Manufacturing example B-6: Synthesis of amorphous polyester resin B-6) In a four-necked flask equipped with a nitrogen inlet tube, dehydration tube, stirrer, and thermocouple, 493 parts of 2 molar bisphenol A propylene oxide adduct (manufactured by Sanyo Chemical Industries, Ltd.), 116 parts of plant-derived succinic acid (manufactured by Tokyo Chemical Industries, Ltd.), 223 parts of plant-derived abietic acid (manufactured by Tokyo Chemical Industries, Ltd.), and 168 parts of recycled PET (manufactured by Kyoei J&T Environmental Co., Ltd.) were charged. The mixture was reacted with titanium tetraisopropoxide (500 ppm relative to the resin component) at atmospheric pressure and 230°C for 10 hours, followed by a further reaction under reduced pressure of 10 mmHg to 15 mmHg for 6 hours. After that, 5 parts of trimellitic anhydride were added to the reaction vessel and the mixture was reacted at 180°C and atmospheric pressure for 3 hours to obtain [amorphous polyester resin B-6]. The composition and physical properties of this resin are shown in Tables 3 and 4 below.
[0310] (Manufacturing example B-7: Synthesis of amorphous polyester resin B-7) In a four-necked flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple, 576 parts of bisphenol A propylene oxide 2 molar adduct (manufactured by Sanyo Chemical Industries, Ltd.), 294 parts of adipic acid (manufactured by Hayashi Pure Chemical Industries, Ltd.), and 129 parts of recycled PET (manufactured by Kyoei J&T Environmental Co., Ltd.) were charged. These were reacted with titanium tetraisopropoxide (500 ppm relative to the resin component) at atmospheric pressure and 230°C for 10 hours, followed by a further reaction under reduced pressure of 10 mmHg to 15 mmHg for 6 hours. Then, 5 parts of trimellitic anhydride were added to the reaction vessel, and the mixture was reacted at 180°C and atmospheric pressure for 3 hours to obtain [amorphous polyester resin B-7]. The composition and physical properties of this resin are shown in Tables 3 and 4 below.
[0311] (Manufacturing example B-8: Synthesis of amorphous polyester resin B-8) In a four-necked flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple, 592 parts of bisphenol A propylene oxide 2 molar adduct (manufactured by Sanyo Chemical Industries, Ltd.), 242 parts of adipic acid (manufactured by Hayashi Pure Chemical Industries, Ltd.), 49 parts of plant-derived succinic acid (manufactured by Tokyo Chemical Industries, Ltd.), and 118 parts of recycled PET (manufactured by Kyoei J&T Environmental Co., Ltd.) were charged. The mixture was reacted with titanium tetraisopropoxide (500 ppm relative to the resin component) at atmospheric pressure and 230°C for 10 hours, followed by a further reaction under reduced pressure of 10 mmHg to 15 mmHg for 6 hours. After that, 5 parts of trimellitic anhydride were added to the reaction vessel and the mixture was reacted at 180°C and atmospheric pressure for 3 hours to obtain [amorphous polyester resin B-8]. The composition and physical properties of this resin are shown in Tables 3 and 4 below.
[0312] (Manufacturing example B-9: Synthesis of amorphous polyester resin B-9) In a four-necked flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple, 376 parts of bisphenol A ethylene oxide 2 molar adduct (manufactured by Sanyo Chemical Industries, Ltd.), 264 parts of bisphenol A propylene oxide 2 molar adduct (manufactured by Sanyo Chemical Industries, Ltd.), 168 parts of adipic acid (manufactured by Hayashi Pure Chemical Industries, Ltd.), and 191 parts of terephthalic acid (manufactured by Toray Industries, Inc.) were charged. These were reacted with titanium tetraisopropoxide (500 ppm relative to the resin component) at atmospheric pressure and 230°C for 10 hours, followed by a further reaction under reduced pressure of 10 mmHg to 15 mmHg for 6 hours. After that, 5 parts of trimellitic anhydride were added to the reaction vessel and the mixture was reacted at 180°C and atmospheric pressure for 3 hours to obtain [amorphous polyester resin B-9]. The composition and physical properties of this resin are shown in Tables 3 and 4 below.
[0313] (Manufacturing example B-10: Synthesis of amorphous polyester resin B-10) In a four-necked flask equipped with a nitrogen inlet tube, dehydration tube, stirrer, and thermocouple, 33 parts of plant-derived 1,3-butanediol (manufactured by Daicel Corporation), 574 parts of bisphenol A propylene oxide 2 molar adduct (manufactured by Sanyo Chemical Industries, Ltd.), 243 parts of plant-derived succinic acid (manufactured by Tokyo Chemical Industries, Ltd.), 87 parts of plant-derived dodecanediic acid (manufactured by Tokyo Chemical Industries, Ltd.), and 62 parts of recycled PET (manufactured by Kyoei J&T Environmental Co., Ltd.) were charged. The mixture was reacted with titanium tetraisopropoxide (500 ppm relative to the resin component) at atmospheric pressure and 230°C for 10 hours, and then further reacted under reduced pressure of 10 mmHg to 15 mmHg for 6 hours. After that, 5 parts of trimellitic anhydride were added to the reaction vessel and the mixture was reacted at 180°C and atmospheric pressure for 3 hours to obtain [amorphous polyester resin B-10]. The composition and physical properties of this resin are shown in Tables 3 and 4 below.
[0314] [Table 3]
[0315] [Table 4]
[0316] (Preparation Example 1-1: Preparation of Amorphous Polyester Resin B Dispersion 1) 150 parts of [amorphous polyester resin B-1], 150 parts of methyl erketone, and 0.1 parts of sodium hydroxide (0.3N) were placed in a 500 ml separable flask and stirred with a Three-One Motor (manufactured by Shinto Kagaku Co., Ltd.) to prepare a resin mixture. While further stirring this resin mixture, 700 parts of ion-exchanged water were gradually added to induce phase inversion emulsification and desolvent removal to obtain [amorphous polyester resin B dispersion 1]. The volume-average particle size of the resin particles in the obtained [amorphous polyester resin B dispersion 1] was 50 nm, and the solid content concentration was 25%. The composition and physical properties of this dispersion are shown in Table 5.
[0317] (Preparation Example 1-2: Preparation of Amorphous Polyester Resin B Dispersion 2) Amorphous polyester resin B dispersion 2 was obtained in the same manner as in Preparation Example 1-1, except that [amorphous polyester resin B-1] was replaced with [amorphous polyester resin B-2]. The volume-average particle size of the resin particles in the obtained Amorphous polyester resin B dispersion 2 was 62 nm, and the solid content concentration was 25%. The composition and physical properties of this dispersion are shown in Table 5.
[0318] (Preparation Examples 1-3: Preparation of Amorphous Polyester Resin B Dispersion 3) In Preparation Example 1-1, [Amorphous Polyester Resin B Dispersion 3] was obtained using the same method as in Preparation Example 1-1, except that [Amorphous Polyester Resin B-1] was replaced with [Amorphous Polyester Resin B-3]. The volume-average particle size of the resin particles in the obtained [Amorphous Polyester Resin B Dispersion 3] was 45 nm, and the solid content concentration was 25%. The composition and physical properties of this dispersion are shown in Table 5.
[0319] (Preparation Examples 1-4: Preparation of Amorphous Polyester Resin B Dispersion 4) Amorphous polyester resin B dispersion 4 was obtained in the same manner as in Preparation Example 1-1, except that [amorphous polyester resin B-1] was replaced with [amorphous polyester resin B-4]. The volume-average particle size of the resin particles in the obtained Amorphous polyester resin B dispersion 4 was 40 nm, and the solid content concentration was 25%. The composition and physical properties of this dispersion are shown in Table 5.
[0320] (Preparation Examples 1-5: Preparation of Amorphous Polyester Resin B Dispersion 5) Amorphous polyester resin B dispersion 5 was obtained in the same manner as in Preparation Example 1-1, except that [amorphous polyester resin B-1] was replaced with [amorphous polyester resin B-5]. The volume-average particle size of the resin particles in the obtained Amorphous polyester resin B dispersion 5 was 40 nm, and the solid content concentration was 25%. The composition and physical properties of this dispersion are shown in Table 5.
[0321] (Preparation Examples 1-6: Preparation of Amorphous Polyester Resin B Dispersion 6) Amorphous polyester resin B dispersion 6 was obtained in the same manner as in Preparation Example 1-1, except that [amorphous polyester resin B-1] was replaced with [amorphous polyester resin B-6]. The volume-average particle size of the resin particles in the obtained Amorphous polyester resin B dispersion 6 was 45 nm, and the solid content concentration was 25%. The composition and physical properties of this dispersion are shown in Table 5.
[0322] (Preparation Examples 1-7: Preparation of amorphous polyester resin B dispersion 7) Amorphous polyester resin B dispersion 7 was obtained in the same manner as in Preparation Example 1-1, except that [amorphous polyester resin B-1] was replaced with [amorphous polyester resin B-7]. The volume-average particle size of the resin particles in the obtained Amorphous polyester resin B dispersion 7 was 75 nm, and the solid content concentration was 25%. The composition and physical properties of this dispersion are shown in Table 5.
[0323] (Preparation Examples 1-8: Preparation of Amorphous Polyester Resin B Dispersion 8) In Preparation Example 1-1, [Amorphous Polyester Resin B Dispersion 8] was obtained using the same method as in Preparation Example 1-1, except that [Amorphous Polyester Resin B-1] was replaced with [Amorphous Polyester Resin B-8]. The volume-average particle size of the resin particles in the obtained [Amorphous Polyester Resin B Dispersion 8] was 64 nm, and the solid content concentration was 25%. The composition and physical properties of this dispersion are shown in Table 5.
[0324] (Preparation Examples 1-9: Preparation of Amorphous Polyester Resin B Dispersion 9) Amorphous polyester resin B dispersion 9 was obtained in the same manner as in Preparation Example 1-1, except that [amorphous polyester resin B-1] was replaced with [amorphous polyester resin B-9]. The volume-average particle size of the resin particles in the obtained Amorphous polyester resin B dispersion 9 was 70 nm, and the solid content concentration was 25%. The composition and physical properties of this dispersion are shown in Table 5.
[0325] (Preparation Examples 1-10: Preparation of amorphous polyester resin B dispersion 10) Amorphous polyester resin B dispersion 10 was obtained in the same manner as in Preparation Example 1-1, except that [amorphous polyester resin B-1] was replaced with [amorphous polyester resin B-10]. The volume-average particle size of the resin particles in the obtained Amorphous polyester resin B dispersion 10 was 48 nm, and the solid content concentration was 25%. The composition and physical properties of this dispersion are shown in Table 5.
[0326] The amorphous polyester resin B dispersions obtained in Preparation Examples 1-1 to 1-10 are summarized in Table 5 below.
[0327] [Table 5]
[0328] (Manufacturing example C-1: Synthesis of crystalline polyester resin C-1) In a 5L four-necked flask equipped with a nitrogen inlet tube, dehydration tube, stirrer, and thermocouple, plant-derived sebacic acid (manufactured by Ogura Synthetic Industry Co., Ltd.) and plant-derived ethylene glycol (manufactured by India Glycols Ltd.) were charged so that the molar ratio of hydroxyl groups to carboxyl groups, [OH / COOH], was 0.9. This mixture was then reacted with titanium tetraisopropoxide (500 ppm relative to the resin component) at 180°C for 10 hours, then the temperature was raised to 200°C for 3 hours, and finally the mixture was reacted at a pressure of 8.3 kPa for 2 hours to obtain [crystalline polyester resin C-1]. The physical properties of this resin are shown in Table 6 below.
[0329] (Manufacturing example C-2: Synthesis of crystalline polyester resin C-2) Crystalline polyester resin C-2 was obtained in the same manner as in Production Example C-1, except that the plant-derived ethylene glycol used as the diol component was replaced with 1,6-hexanediol (manufactured by Tokyo Chemical Industry Co., Ltd.). The physical properties of this resin are shown in Table 6 below.
[0330] (Manufacturing example C-3: Synthesis of crystalline polyester resin C-3) Crystalline polyester resin C-3 was obtained in the same manner as in Production Example C-1, except that plant-derived sebacic acid, used as the dicarboxylic acid component, was replaced with plant-derived dodecanediic acid (manufactured by Tokyo Chemical Industry Co., Ltd.). The physical properties of this resin are shown in Table 6 below.
[0331] [Table 6]
[0332] (Preparation Example 2-1: Preparation of crystalline polyester resin C dispersion 1) 45 parts of [crystalline polyester resin C-1] and 450 parts of ethyl acetate were placed in a container equipped with a stirring rod and a thermometer. The mixture was heated to 80°C under stirring and maintained at 80°C for 5 hours. After cooling to 30°C in 1 hour, the mixture was dispersed using a bead mill (Ultraviscomill, manufactured by AIMEX) under the following conditions: liquid transfer rate of 1 kg / hour, disk peripheral speed of 6 m / second, and 80% by volume filling with 0.5 mm diameter zirconia beads, in 3 passes, to obtain [crystalline polyester resin C dispersion 1]. The volume-average particle size of the obtained crystalline polyester resin particles was 350 nm, and the solid content concentration of the resin particles was 10%. The composition and physical properties of this dispersion are shown in Table 7.
[0333] (Preparation Example 2-2: Preparation of crystalline polyester resin C dispersion 2) Crystalline polyester resin C dispersion 2 was obtained in the same manner as in Preparation Example 2-1, except that [crystalline polyester resin C-1] was replaced with [crystalline polyester resin C-2]. The volume-average particle size of the obtained crystalline polyester resin particles was 350 nm, and the solid content concentration of the resin particles was 10%. The composition and physical properties of this dispersion are shown in Table 7.
[0334] (Preparation Example 2-3: Preparation of crystalline polyester resin C dispersion 3) In Preparation Example 2-1, [Crystalline Polyester Resin C Dispersion 3] was obtained using the same method as in Preparation Example 2-1, except that [Crystalline Polyester Resin C-1] was replaced with [Crystalline Polyester Resin C-3]. The volume-average particle size of the resin particles in the obtained [Crystalline Polyester Resin C Dispersion 3] was 360 nm, and the solid content concentration was 10%. The composition and physical properties of this dispersion are shown in Table 7.
[0335] The crystalline polyester resin C dispersions obtained in Preparation Examples 2-1 to 2-3 are summarized in Table 7 below.
[0336] [Table 7]
[0337] (Preparation Example 3-1: Preparation of Masterbatch 1) 500 parts water, 500 parts carbon black (Printex35, manufactured by Dexa) [DBP oil absorption = 42 mL / 100 mg, pH = 9.5], and 500 parts [amorphous polyester resin A-9] were added and mixed in a Henschel mixer (manufactured by Nippon Coke Industries Co., Ltd.). The mixture was kneaded at 150°C for 30 minutes using two rolls, then rolled and cooled, and pulverized in a pulperizer to obtain [Masterbatch 1]. The composition is shown in Table 8 below.
[0338] (Preparation Example 3-2: Preparation of Masterbatch 2) Masterbatch 2 was obtained in the same manner as in Preparation Example 3-1, except that [amorphous polyester resin A-9] was changed to [amorphous polyester resin A-4]. The composition is shown in Table 8 below.
[0339] The masterbatches obtained in Preparation Example 3-1 and Preparation Example 3-2 are summarized in Table 8 below.
[0340] [Table 8]
[0341] (Preparation Example 4-1: Preparation of Wax Dispersion 1) Fifty parts of ester wax (WE-11, manufactured by NOF Corporation, a synthetic wax derived from plant monomers, melting point 70°C) and 450 parts of ethyl acetate were charged into a container equipped with a stirring rod and thermometer. The mixture was heated to 80°C under stirring and maintained at 80°C for 5 hours, then cooled to 30°C in 1 hour. Dispersion was performed using a bead mill (UltraViscomill, manufactured by AIMEX Corporation) under the following conditions: liquid transfer rate of 1 kg / hour, disk peripheral speed of 6 m / second, and 80% by volume filling of 0.5 mm diameter zirconia beads, in 3 passes, to obtain [Wax Dispersion 1]. The volume-average particle size of the wax particles in the obtained [Wax Dispersion 1] was 420 nm, and the solid content concentration of the resin particles was 25%. The composition and physical properties are shown in Table 9.
[0342] (Preparation Example 4-2: Preparation of Wax Dispersion 2) [Wax Dispersion 2] was obtained in the same manner as in Preparation Example 4-1, except that the ester wax was replaced with paraffin wax (HNP-9, manufactured by Nippon Seiro Co., Ltd., hydrocarbon wax, melting point 75°C). The volume-average particle size of the wax particles in the obtained [Wax Dispersion 2] was 480 nm, and the solid content concentration of the resin particles was 25%. The composition and physical properties are shown in Table 9.
[0343] The wax dispersions obtained in Preparation Examples 4-1 and 4-2 are summarized in Table 9 below.
[0344] [Table 9]
[0345] (Example 1) <Preparation of the oil phase> 50 parts of [wax dispersion 1], 670 parts of [amorphous polyester resin A-1], 50 parts of [crystalline polyester resin C dispersion 1], and 90 parts of [masterbatch 1] (pigment) were placed in a container and mixed at 7,000 rpm for 60 minutes using a TK homomixer (manufactured by Primix Corporation) to obtain [oil phase 1]. The amounts of each ingredient listed represent the amount of solids in each raw material, and the same applies to the following processes.
[0346] <Preparation of the aqueous phase> 990 parts water, 25 parts sodium dodecyl sulfate, and 90 parts ethyl acetate were mixed and stirred to obtain a milky white liquid. This was designated as [Aqueous Phase 1].
[0347] <Phase inversion emulsification> [Oil phase 1] 700 parts were mixed in a TK homomixer at a rotation speed of 5,000 rpm while 20 parts of 28% ammonia water were added and mixed for 10 minutes. Then, 1,200 parts of [Aqueous phase 1] were gradually added dropwise to obtain [Emulsified slurry 1].
[0348] <Solvent removal> [Emulsified slurry 1] was placed in a container equipped with a stirrer and thermometer, and desolvented at 30°C for 180 minutes to obtain [Desolvented slurry 1]. The volume-average particle size of the particles contained in [Desolvented slurry 1] was 0.35 μm.
[0349] <Agglutination> Fifty parts of a 10% magnesium sulfate solution were added dropwise to [Solvent-removing slurry 1] and stirred for a further 5 minutes. The temperature was then raised to 50°C, and when the particle size reached 5.0 μm, 140 parts of [Amorphous polyester resin B dispersion 1] were added dropwise and stirred for 30 minutes. After that, 100 parts of a 10% sodium sulfate aqueous solution were added to complete the flocculation process and obtain [Flocculated slurry 1].
[0350] <Fusion> [Agglomerated slurry 1] was heated to 70°C while stirring, and cooled when it reached the desired average circularity of 0.960 to obtain [Dispersed slurry 1].
[0351] <Washing and drying> After filtering 100 parts of [Dispersed Slurry 1] under reduced pressure, the following operations (1) to (4) were performed twice to obtain [Filtration Cake 1]. (1): 100 parts of deionized water were added to the filter cake, mixed with a TK homomixer (rotating at 12,000 rpm for 10 minutes), and then filtered. (2): 100 parts of a 10% sodium hydroxide aqueous solution were added to the filtration cake from (1) above, and the mixture was mixed in a TK homomixer (at a rotation speed of 12,000 rpm for 30 minutes), and then filtered under reduced pressure. (3): 100 parts of 10% hydrochloric acid were added to the filtered cake from (2) above, and the mixture was mixed in a TK homomixer (at a rotation speed of 12,000 rpm for 10 minutes), and then filtered. (4): 300 parts of deionized water were added to the filtration cake from (3) above, mixed with a TK homomixer (rotating at 12,000 rpm for 10 minutes), and then filtered. The obtained [filter cake 1] was dried in a circulating air dryer at 45°C for 48 hours, and then sieved with a mesh with a mesh opening of 75 μm to obtain [matrix resin particles 1].
[0352] <External additive treatment process> To 100 parts of [matrix resin particles 1], 2.0 parts of hydrophobic silica (HDK® H2000, manufactured by Clariant Co., Ltd.) was added as an external additive and mixed in a Henschel mixer. The mixture was then passed through a sieve with a mesh size of 50 μm to obtain [resin particles 1].
[0353] The ratio of environmentally friendly components in [Resin Particle 1] was calculated using the following formula (VI). ([Amorphous polyester resin A-1] environmentally friendly component ratio × parts by weight + [Crystalline polyester resin C-1] environmentally friendly component ratio × parts by weight + [Wax 1] environmentally friendly component ratio × parts by weight + [Amorphous polyester resin B-1] environmentally friendly component ratio × parts by weight) / ([Amorphous polyester resin A-1] parts by weight + [Crystalline polyester resin C-1] parts by weight + [Wax 1] parts by weight + [Amorphous polyester resin B-1] parts by weight) × 100 ... (VI)
[0354] (Example 2) In Example 1, [wax dispersion 1] was changed to [wax dispersion 2] in the <oil phase preparation> step, [crystalline polyester resin C dispersion 1] was changed to [crystalline polyester resin C dispersion 2], and [masterbatch 1] was changed to [masterbatch 2]. In addition, in the <aggregation> step, [amorphous polyester resin B dispersion 1] was changed to [amorphous polyester resin B dispersion 2]. Otherwise, [resin particles 2] were obtained in the same manner as in Example 1.
[0355] (Example 3) In the oil phase preparation of Example 1, 670 parts of [amorphous polyester resin A-1] were changed to 550 parts of [amorphous polyester resin A-2], 50 parts of [wax dispersion 1] were changed to 90 parts, and 50 parts of [crystalline polyester resin C dispersion 1] were changed to 90 parts. In the aggregation stage, 140 parts of [amorphous polyester resin B dispersion 1] were changed to 180 parts. Otherwise, [resin particles 3] were obtained in the same manner as in Example 1.
[0356] (Example 4) In the oil phase preparation of Example 1, 670 parts of [amorphous polyester resin A-1] were changed to 640 parts of [amorphous polyester resin A-3], 50 parts of [wax dispersion 1] were changed to 110 parts, and 50 parts of [crystalline polyester resin C dispersion 1] were changed to 110 parts of [crystalline polyester resin C dispersion 3]. Except for these changes, in the aggregation stage, 140 parts of [amorphous polyester resin B dispersion 1] were changed to 50 parts of [amorphous polyester resin B dispersion 3], the same procedure as in Example 1 was used to obtain [resin particles 4].
[0357] (Example 5) In Example 1, [amorphous polyester resin A-1] was changed to [amorphous polyester resin A-4] in the <oil phase preparation> step, and [crystalline polyester resin C dispersion 1] was changed to [crystalline polyester resin C dispersion 3]. In addition, in the <aggregation> step, [amorphous polyester resin B dispersion 1] was changed to [amorphous polyester resin B dispersion 4]. Otherwise, [resin particles 5] were obtained in the same manner as in Example 1.
[0358] (Example 6) In the oil phase preparation of Example 1, 670 parts of [amorphous polyester resin A-1] were changed to 640 parts of [amorphous polyester resin A-5], 50 parts of [wax dispersion 1] were changed to 110 parts, 50 parts of [crystalline polyester resin C dispersion 1] were changed to 110 parts, and [masterbatch 1] was changed to [masterbatch 2]. In the aggregation stage, 140 parts of [amorphous polyester resin B dispersion 1] were changed to 50 parts of [amorphous polyester resin B dispersion 3]. In short, [resin particles 6] were obtained in the same manner as in Example 1.
[0359] (Example 7) In the oil phase preparation of Example 1, the amount of [amorphous polyester resin A-1] was changed from 670 parts to 640 parts, [wax dispersion 1] was changed from 50 parts to 110 parts to [wax dispersion 2], and [crystalline polyester resin C dispersion 1] was changed from 50 parts to 110 parts. In the aggregation stage, the amount of [amorphous polyester resin B dispersion 1] was changed from 140 parts to 50 parts to [amorphous polyester resin B dispersion 3]. In short, [resin particles 7] were obtained in the same manner as in Example 1.
[0360] (Example 8) In Example 1, the oil phase preparation was changed from 670 parts to 550 parts of [amorphous polyester resin A-1], from 50 parts to 90 parts of [wax dispersion 2], and from 50 parts to 90 parts of [crystalline polyester resin C dispersion 1]. In addition, in the aggregation stage, 140 parts of [amorphous polyester resin B dispersion 1] was changed to 180 parts of [amorphous polyester resin B dispersion 5]. Otherwise, [resin particles 8] were obtained in the same manner as in Example 1.
[0361] (Comparative Example 1) Resin particles 9 were obtained in the same manner as in Example 1, except that [amorphous polyester resin A-1] was changed to [amorphous polyester resin A-6] in the <oil phase preparation> of Example 1.
[0362] (Comparative Example 2) Except for changing [amorphous polyester resin A-1] to [amorphous polyester resin A-7] in the <oil phase preparation> of Example 1, and changing [amorphous polyester resin B dispersion 1] to [amorphous polyester resin B dispersion 6] in the <aggregation>, [resin particles 10] were obtained in the same manner as in Example 1.
[0363] (Comparative Example 3) In the oil phase preparation of Example 1, 670 parts of [amorphous polyester resin A-1] were changed to 740 parts of [amorphous polyester resin A-8], 50 parts of [wax dispersion 1] were changed to 40 parts, 50 parts of [crystalline polyester resin C dispersion 1] were changed to 40 parts, and [masterbatch 1] was changed to [masterbatch 2]. In the aggregation stage, 140 parts of [amorphous polyester resin B dispersion 1] were changed to 90 parts of [amorphous polyester resin B dispersion 7]. In short, [resin particles 11] were obtained in the same manner as in Example 1.
[0364] (Comparative Example 4) In the oil phase preparation of Example 1, the amount of [amorphous polyester resin A-1] was changed from 670 parts to 640 parts, the amount of [wax dispersion 1] was changed from 50 parts to 110 parts to [wax dispersion 2], and the amount of [crystalline polyester resin C dispersion 1] was changed from 50 parts to 110 parts to [crystalline polyester resin C dispersion 3]. Except for these changes, the [resin particles 12] were obtained in the same manner as in Example 1.
[0365] (Comparative Example 5) In Example 1, [amorphous polyester resin A-1] was changed to [amorphous polyester resin A-8] in the <oil phase preparation>, [wax dispersion 1] was changed to [wax dispersion 2], and [crystalline polyester resin C dispersion 1] was changed to [crystalline polyester resin C dispersion 2]. In addition, in the <aggregation>, [amorphous polyester resin B dispersion 1] was changed to [amorphous polyester resin B dispersion 8]. Otherwise, [resin particles 13] were obtained in the same manner as in Example 1.
[0366] (Comparative Example 6) Except for changing [amorphous polyester resin A-1] to [amorphous polyester resin A-9] in the <oil phase preparation> of Example 1, and changing [amorphous polyester resin B dispersion 1] to [amorphous polyester resin B dispersion 9] in the <aggregation>, [resin particles 14] were obtained in the same manner as in Example 1.
[0367] (Comparative Example 7) In Example 1, [amorphous polyester resin A-1] was changed to [amorphous polyester resin A-9] and [masterbatch 1] to [masterbatch 2] in the <oil phase preparation> step, and in <aggregation>, [amorphous polyester resin B dispersion 1] was changed to [amorphous polyester resin B dispersion 6]. Except for these changes, [resin particles 15] were obtained in the same manner as in Example 1.
[0368] (Comparative Example 8) In the oil phase preparation of Example 1, 670 parts of [amorphous polyester resin A-1] were changed to 640 parts of [amorphous polyester resin A-9], 50 parts of [wax dispersion 1] were changed to 90 parts of [wax dispersion 2], and 50 parts of [crystalline polyester resin C dispersion 1] were changed to 90 parts. In the aggregation stage, 140 parts of [amorphous polyester resin B dispersion 1] were changed to 90 parts of [amorphous polyester resin B dispersion 10]. Otherwise, [resin particles 16] were obtained in the same manner as in Example 1.
[0369] (Comparative Example 9) Except for changing [amorphous polyester resin A-1] to [amorphous polyester resin A-9] and [crystalline polyester resin C dispersion 1] to [crystalline polyester resin C dispersion 3] in the <oil phase preparation> of Example 1, [resin particles 17] were obtained in the same manner as in Example 1.
[0370] (Comparative Example 10) In Example 1, [amorphous polyester resin A-1] was changed to [amorphous polyester resin A-7] and [masterbatch 1] to [masterbatch 2] in the <oil phase preparation> step, and in <aggregation>, [amorphous polyester resin B dispersion 1] was changed to [amorphous polyester resin B dispersion 3]. Except for these changes, [resin particles 18] were obtained in the same manner as in Example 1.
[0371] (Comparative Example 11) Except for changing [amorphous polyester resin A-1] to [amorphous polyester resin A-9] in the <oil phase preparation> of Example 1, and changing [amorphous polyester resin B dispersion 1] to [amorphous polyester resin B dispersion 10] in the <aggregation>, [resin particles 19] were obtained in the same manner as in Example 1.
[0372] The composition of the oil phase components and the characteristics of the flocculation process in Examples 1-8 and Comparative Examples 1-11 are shown in Table 10 below.
[0373] [Table 10]
[0374] Furthermore, the environmental compatibility, heat resistance, and filming resistance of each toner obtained in Examples 1-8 and Comparative Examples 1-11 were evaluated using the following methods. The results are shown in Table 11 below.
[0375] <Evaluation Method> <<Environmental Compatibility>> Based on the calculated value of the environmentally friendly component ratio obtained using the above formula (VI), "environmental compatibility" was evaluated according to the following evaluation criteria. - Evaluation Criteria for "Environmental Compatibility" - ○: 50% or more △: 30% or more but less than 50% ×: Less than 30%
[0376] <<Static Stability>> The sample was conditioned in an open system for at least 30 minutes in a room with normal temperature and humidity (temperature 23.5°C, humidity 60%RH). After adding 6,000g of initial resin particles and 0.452g of toner to a stainless steel container, it was sealed and operated for 1 minute at a scale of 150 using a YS-LD (Yayoi Co., Ltd. shaker), resulting in approximately 1100 oscillations and frictional charging. The sample was then measured using a general blow-off method (Toshiba Chemical Co., Ltd.: TB-200). Furthermore, the sample was conditioned in an open system for 24 hours under high temperature and high humidity conditions (temperature 35°C, humidity 70%RH), and then conditioned in an open system for at least 30 minutes in a room with normal temperature and humidity (temperature 23.5°C, humidity 60%RH), and measured similarly. "Charge stability" was evaluated based on the amount of change in charge. - Evaluation Criteria for "Charge Stability" - ○: Less than 5 (μc / g) △: 5 (μc / g) or more and less than 10 (μc / g) ×: 10 (μc / g) or more
[0377] <<Low Temperature Fixation>> A developer was obtained by mixing the carrier used in imagio MP C5503 (manufactured by Ricoh Co., Ltd.) with the resin particles obtained in Examples 1-8 and Comparative Examples 1-11, so that the concentration of the resin particles was 5% by mass. After adding the developer to the imagio MP C5503 unit (manufactured by Ricoh Co., Ltd.), a solid 2cm x 15cm rectangular image was printed on PPC paper type 6000 <70W> A4 T grain (manufactured by Ricoh Co., Ltd.) with a resin particle adhesion amount of 0.40 mg / cm². 2 The image was formed in such a manner. At this time, the surface temperature of the fixing roller was changed, and it was observed whether a cold offset occurred in which the remaining image of the solid color was fixed to a location other than the desired location. The cold offset temperature (lower fixing limit temperature) was determined, and the "low-temperature fixing performance" was evaluated based on the evaluation criteria below. - Evaluation criteria for "low-temperature fixation" - ○: Cold offset temperature is 110°C or higher and less than 120°C △: Cold offset temperature is between 120°C and 130°C. ×: Cold offset temperature is 130°C or higher
[0378] <<Heat-resistant storage stability>> Each resin particle was filled into a 50 mL glass container and left in a 50°C constant temperature bath for 24 hours. The resin particles were then cooled to 24°C, and the penetration depth (mm) was measured using a penetration test (JIS K2235-1991). The "heat resistance to storage" was evaluated based on the following evaluation criteria. A higher penetration depth indicates better heat resistance to storage, and a value of less than 5 mm suggests a high possibility of problems during use. In this specification, penetration depth is expressed as the penetration depth (mm). - Evaluation criteria for "heat resistance and preservation properties" - ○: Needle penetration depth 20mm or more and less than 25mm △: Needle penetration 10mm or more but less than 20mm ×: Needle penetration less than 10mm
[0379] [Table 11]
[0380] Examples of embodiments of the present invention include the following: (1) Resin particles containing at least a binder resin, The resin particles have a core-shell structure consisting of a core layer and a shell layer. The resin forming the core layer contains amorphous polyester resin A and crystalline polyester resin. The resin forming the shell layer contains amorphous polyester resin B. The SP values (SPa) of the amorphous polyester resin A, the SP values (SPb) of the amorphous polyester resin B, and the SP values (SPc) of the crystalline polyester resin satisfy the following relational expressions (1) to (3): The resin particles contain 30% or more of environmentally friendly components. Resin particles characterized by the following features. SPa-SPc≦1.6 (1) 0.2 ≤ SPb - SPa (2) SPb ≤ 11.6 (3) (2) The resin particles according to (1) above, wherein the amorphous polyester resin A contains constituent units derived from a carboxylic acid, and the carboxylic acid contains one or more biomass-derived dicarboxylic acids having 8 or more carbon atoms. (3) The resin particles according to (1) or (2) above, wherein the amorphous polyester resin A and / or amorphous polyester resin B contain sulfo groups. (4) Resin particles according to any one of items (1) to (3) above, wherein the amorphous polyester resin B contains 0% environmentally friendly components. (5) A method for producing resin particles according to any one of (1) to (4) above, characterized by having the following steps a, b, c, and d. Step a: A step of preparing an oil phase by dissolving or dispersing amorphous polyester resin A and crystalline polyester resin in an organic solvent. Step b: A step of adding water to the oil phase to convert the water-in-oil dispersion to an oil-in-water dispersion. Step c: A step of agglomerating the particles of the oil-in-water dispersion. Step d: After step c, an aqueous dispersion of amorphous polyester resin B is added to the aqueous dispersion to aggregate the amorphous polyester resin B and form a shell layer. (6) The method for producing resin particles according to (5) above, wherein the amorphous polyester resin A and / or amorphous polyester resin B contains a sulfo group. (7) Toner resin particles characterized by containing the resin particles described in any one of the above items (1) to (4). (8) A toner characterized by containing the toner resin particles described in (7) above. (9) The toner described in (8) above, further containing an external additive. (10) A method for producing toner, characterized by adding an external additive to the toner resin particles described in (7) above. (11) A developer characterized by containing the toner described in (9) above. (12) A toner storage unit characterized by containing the toner described in (9) above. (13) Electrostatic latent image carrier and An electrostatic latent image forming means for forming an electrostatic latent image on the electrostatic latent image carrier, The developing means comprises a toner that develops the electrostatic latent image formed on the electrostatic latent image carrier to form a visible image, An image forming apparatus characterized in that the toner is the toner described in (9) above. [Explanation of Symbols]
[0381] 10 Photoconductor drum 40 Developer 58 Corona Charger 80 Transfer Rollers 90 Cleaning device 110 Process Cartridges 160Y Sub-hopper (Yellow) 160C Sub-hopper (Cyan) 160M Sub-hopper (Magenta) 160K Sub-hopper (Black) 180Y Image Forming Unit (Yellow) 180C Image Forming Unit (Cyan) 180M Image Forming Unit (Magenta) 180K Image Forming Unit (Black) 200 Image forming apparatus 210 Paper feed section 211 Paper feed cassette 212 Paper feed roller 220 Conveying section 221 Laura 222 Timing Roller 223 Paper output roller 224 Paper Output Tray 230 Image creation section 231Y Photoconductor Drum (Yellow) 231C Photoconductor Drum (Cyan) 231M Photoconductor Drum (Magenta) 231K Photoconductor Drum (Black) 232Y Charger (Yellow) 232C Charger (Cyan) 232M Charger (Magenta) 232K Charger (Black) 233 Exposure Unit 233a light source 233bY Polygon Mirror (Yellow) 233bC Polygon Mirror (Cyan) 233bM Polygon Mirror (Magenta) 233bK Polygon Mirror (Black) 234Y Toner Bottle (Yellow) 234C Toner Bottle (Cyan) 234M Toner Bottle (Magenta) 234K Toner Bottle (Black) 236Y Cleaning device (yellow) 236C Cleaning device (Cyan) 236M Cleaning Machine (Magenta) 236K Cleaning Device (Black) 240 Transfer section 241 Drive roller 242 Driven roller 243 Intermediate transfer belt 244 Primary Transfer Roller 244Y Primary Transfer Roller (Yellow) 244C Primary Transfer Roller (Cyan) 244M Primary Transfer Roller (Magenta) 244K Primary Transfer Roller (Black) 245 Secondary opposing roller 246 Secondary Transfer Roller 250 Fuser 251 Fixing belt 252 Pressure roller L Laser P paper [Prior art documents] [Patent Documents]
[0382] [Patent Document 1] Japanese Patent Publication No. 2023-121119 [Patent Document 2] Japanese Patent Publication No. 2024-077592 [Patent Document 3] Japanese Patent Publication No. 2024-098761
Claims
1. Resin particles containing at least a binder resin, The resin particles have a core-shell structure consisting of a core layer and a shell layer. The resin forming the core layer contains amorphous polyester resin A and crystalline polyester resin. The resin forming the shell layer contains amorphous polyester resin B. The SP value (SPa) of the amorphous polyester resin A, the SP value (SPb) of the amorphous polyester resin B, and the SP value (SPc) of the crystalline polyester resin satisfy the following relational expressions (1) to (3): The resin particles contain 30% or more of environmentally friendly components. Resin particles characterized by the following features. SPa-SPc≦1.6 (1) 0.2≦SPb-SPa (2) SPb ≤ 11.6 (3)
2. The resin particles according to claim 1, wherein the amorphous polyester resin A contains constituent units derived from a carboxylic acid, and the carboxylic acid contains one or more biomass-derived dicarboxylic acids having 8 or more carbon atoms.
3. The resin particles according to claim 1, wherein the amorphous polyester resin A and / or amorphous polyester resin B contains a sulfo group.
4. The resin particles according to claim 1, wherein the amorphous polyester resin B contains 0% environmentally friendly components.
5. A method for producing resin particles according to any one of claims 1 to 4, characterized by having the following steps a, b, c, and d. Step a: A step of preparing an oil phase by dissolving or dispersing amorphous polyester resin A and crystalline polyester resin in an organic solvent. Step b: A step of adding water to the oil phase to convert the water-in-oil dispersion into an oil-in-water dispersion. Step c: A step of agglomerating the particles of the oil-in-water dispersion. Step d: After step c, an aqueous dispersion of amorphous polyester resin B is added to the aqueous dispersion to aggregate the amorphous polyester resin B and form a shell layer.
6. The method for producing resin particles according to claim 5, wherein the amorphous polyester resin A and / or amorphous polyester resin B contains a sulfo group.
7. Toner resin particles characterized by containing resin particles according to any one of claims 1 to 4.
8. A toner characterized by containing the resin particles for toner described in claim 7.
9. The toner according to claim 8, further containing an external additive.
10. A method for producing toner, characterized by adding an external additive to the toner resin particles described in claim 7.
11. A developer characterized by containing the toner described in claim 9.
12. A toner storage unit characterized by storing the toner described in claim 9.
13. Electrostatic latent image carrier, An electrostatic latent image forming means for forming an electrostatic latent image on the electrostatic latent image carrier, The developing means comprises a toner that develops the electrostatic latent image formed on the electrostatic latent image carrier to form a visible image, An image forming apparatus characterized in that the toner is the toner described in claim 9.
Citation Information
Patent Citations
JP2023‐121119A
JP2024‐098761A
JP2024‐077592A